A tissue filling material for orthopedics

By using a composite material of cuttlefish bone mineral powder, bovine or porcine cancellous bone mineral particles and calcium sulfate, the problem of existing bone graft replacement materials being difficult to combine multiple properties is solved, and rapid dissolution and formation in the body is achieved. A suitable microenvironment promotes bone repair and new bone formation.

CN118416307BActive Publication Date: 2025-01-24NINGBO BEILUN CHANGZHENG ORTHOPEDIC HOSPITAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410488707.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-04-23
Publication Date
2025-01-24
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

Existing bone graft alternative materials are difficult to combine good three-dimensional interoperable mesh structure, mechanical strength, degradability and osteogenic activity, and cannot effectively support the bone repair process and new bone formation.

Method used

Use cuttlefish ore ore, cattle or pork pine bone ore granules and calcium sulfate as the main ingredient. The pH value of the liquid molten bone ore is formed by adding a pH value of the liquid bone ore as the main structure. Calcium sulfate and cuttlefish bone ore are composite granular materials for composite coating.

Benefits of technology

The rapid solubility in the body is achieved, and the micro -alkaline environment of a stable high -calcium high -lying magnesium rich is formed. It provides a suitable biochemical foundation to promote bone repair and new bone formation, while maintaining a good three -dimensional pore structure and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118416307B_ABST
    Figure CN118416307B_ABST
Patent Text Reader

Abstract

The invention discloses an orthopedic tissue filling material, wherein the raw materials include cuttlefish bone mineral powder, bovine or porcine cancellous bone mineral particles and calcium sulfate, wherein the mass ratio of cuttlefish bone mineral powder to calcium sulfate is 1:1-10, and the mass ratio of the total mass of cuttlefish bone mineral powder + calcium sulfate to the bovine or porcine cancellous bone mineral particles is 1:1-5. The invention can provide space for new bone formation and form a stable local high-calcium and magnesium-rich microenvironment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical material production, in particular to a tissue filling material for orthopedics. Background Art

[0002] Bone transplantation is a common tissue transplantation, second only to blood transfusion. Autologous bone transplantation is the gold standard for bone defect repair. This is because the three essential elements of autologous bone repair include cells, active proteins, and a mineralized extracellular matrix scaffold. The primary component is hydroxyapatite, which also includes other ions such as Mg, Fe, Si, Zn, Mn, Cu, Na, K, F, S, C, and Cl. The research and development of bone graft replacement materials is currently a major focus of medical research. Human bone mineralization undergoes extensive homogeneous replacement, and human bone possesses a complex composition and structure. The design of bone graft replacement materials (artificial bone) or bone tissue engineering scaffolds critically considers the complex composition and structure (unique three-dimensional interconnected pore structure and natural nanocrystalline structure) of human bone, a heavily mineralized tissue, as well as its physicochemical properties, such as hydrophilicity.

[0003] Human bone cannot be completely replaced by the limited properties provided by a single material. More importantly, the ideal artificial bone or bone tissue engineering scaffold must provide a three-dimensional porous microstructure for bone tissue regeneration and provide space for the adhesion and physiological activities of osteoblast-related cells. At the same time, the scaffold must have a composition similar to that of human bone mineral. The dissolution of the scaffold, including the physical, chemical and cellular dissolution, can provide calcium, phosphorus ions and other osteogenic active ions such as calcium and magnesium ions, just like the dissolution of autologous bone mineralized extracellular matrix scaffolds, forming a high-calcium and osteogenic active ion-rich microenvironment.

[0004] Calcium and phosphorus are the main components of human bone mineral and are currently the most common components of bone graft substitutes in clinical practice. Currently, there is a lack of ideal bone graft substitutes in clinical practice. This is primarily due to the inability to combine ideal three-dimensional interconnected pore structures, high porosity and specific surface area, appropriate degradability, good hydrophilicity, osteoconductivity, osteoinductivity, and mechanical strength. An ideal three-dimensional interconnected pore structure is the most fundamental requirement for bone tissue engineering scaffolds or bone graft substitutes. Clinically used artificial bones with relatively ideal three-dimensional interconnected pore microstructures are all derived from animal materials. Two of these are porous hydroxyapatite ceramics derived from bovine cancellous bone via high-temperature sintering. This includes the Swiss Geistlich artificial bone material, the best-selling in my country. These materials are characterized by their composition, structure, and pore size highly similar to the mineralized extracellular matrix of human cancellous bone, resulting in excellent biocompatibility and osteoconductivity. Implantation in the body facilitates the recruitment of bone repair cells, the adhesion of active factors, the exchange of oxygen and tissue fluid, and the formation and entry of blood vessels, providing excellent adhesion support and physiological activity for bone repair cells. However, their significant drawback is that hydroxyapatite, the bone mineral derived from high-temperature sintering of bovine cancellous bone, is extremely stable and degrades slowly in vivo. It has the lowest solubility among calcium-phosphate bone graft materials, and its degradation rate far exceeds the rate of new bone formation. Furthermore, it cannot continuously release high concentrations of osteogenic ions such as calcium and phosphorus, resulting in a lack of robust osteogenic activity. The core mechanism of bioactivity of calcium-phosphate bone graft substitutes is the partial dissolution and release of ion products in the body, which increases local calcium and phosphate ion concentrations and precipitates bioapatite on the ceramic surface. Octacalcium phosphate (OCP) is generally formed in an environment with a pH value less than 9.25, while HAp is preferentially formed at higher pH values.

[0005] Calcium sulfate is the earliest bone graft replacement material and is currently second only to calcium-phosphate materials in terms of application. It exhibits excellent degradation properties and can form a localized high-calcium environment with potential osteogenic activity. However, its strength is insufficient to construct a three-dimensional interconnected scaffold. Furthermore, it generally degrades faster than bone repair, hindering the provision of sufficient spatial and temporal support for bone repair during bone graft replacement. Furthermore, its dissolution and degradation process creates a slightly acidic environment, whereas a slightly alkaline environment is more conducive to promoting new bone formation.

[0006] Another hot topic in artificial bone research over the past decade has been the study of the effects of metal ion doping on osteoblastic activity. A review summarizes how metal ions regulate bone formation by promoting or inhibiting various key processes involved in bone formation and repair, including stem cell proliferation and osteogenic differentiation, osteoblast physiological activity and differentiation, bone formation and mineralization, and inhibition of osteoclast differentiation, as well as vascular endothelial cells.

[0007] Calcium is the most common mineral in the human body and is primarily stored in bone. Calcium homeostasis is tightly regulated by parathyroid hormone (PTH) and calcitonin, which regulate serum calcium levels by stimulating (PTH) or inhibiting (calcitonin) bone resorption by osteoclasts. During bone remodeling, bone-resorbing osteoclasts generate local concentrations of extracellular calcium ions that can reach 40 mol / L. This increased calcium in the microenvironment inhibits the resorptive activity of osteoclasts and promotes the proliferation and differentiation of mesenchymal cells into stromal cells and osteoblasts. In the 1980s, extracellular calcium was shown to activate extracellular calcium protein-coupled receptors, termed calcium sensor receptors (CaSRs). Regarding the hyperresponsiveness of osteocytes to extracellular calcium, elevated calcium levels promote osteocyte proliferation, chemotaxis, and osteogenic differentiation, and activate bone marrow-derived mesenchymal stromal cells in a dose-dependent manner via CaSR activation.

[0008] Strontium (SR) is a critical trace element in the human body and a vital component of bones and teeth. It participates in bone formation, stimulating bone formation and inhibiting bone resorption. Among the trace metals in human bone, strontium is the only one associated with bone compressive strength, accounting for approximately 0.01% of bone mass, with an adult human containing approximately 320 mg. Strontium is in the same group as calcium (Ca) in the periodic table, sharing similar chemical properties and being an osteophilic element. Although SR ions are present in much lower concentrations than Ca ions in the body, their osteogenic effects have been demonstrated: they promote osteoblast proliferation and inhibit osteoclast differentiation and function, promoting bone formation, slowing bone resorption, and improving bone microstructure.

[0009] Magnesium ions are currently a hotly researched and clinically applied osteogenic ion. Magnesium is widely present in nature, with an adult human containing approximately 25g of magnesium. Magnesium plays a crucial role in bone formation and all growth processes, maintaining bone cell structure and function, bone metabolism, and remodeling. Low-magnesium magnesium phosphate-based bone cements can significantly enhance cell adhesion. Magnesium-doped calcium phosphate bone cements are gaining increasing attention as a new bone repair biomaterial because they promote the formation of a bony interface between implant materials and bone tissue. Magnesium-doped bone cements are relatively easy to formulate, with a formula of 73% β-tricalcium phosphate / 21% monocalcium phosphate / 5% magnesium dihydrogen phosphate already in clinical use in countries such as New Zealand. Composite magnesium-containing bone cements are biodegradable, releasing calcium, phosphorus, and magnesium, which are beneficial elements for bone formation. After implantation, they undergo degradation and ion exchange within the body. However, they lack a three-dimensional interconnected pore structure, hindering the early penetration of repair cells and blood vessels into the graft. Summary of the Invention

[0010] The purpose of the present invention is to provide an orthopedic tissue filling material that can provide space for new bone formation and form a stable slightly alkaline environment with high calcium, high strontium, rich magnesium and other osteogenic active ions.

[0011] The technical solution adopted by the present invention to solve its technical problem is:

[0012] An orthopedic tissue filler material prepared from cuttlefish bone mineral powder, bovine or porcine cancellous bone granules, and calcium sulfate. The mass ratio of cuttlefish bone mineral powder to calcium sulfate is 1:1-10, and the mass ratio of the combined mass of cuttlefish bone mineral powder and calcium sulfate to the bovine or porcine cancellous bone granules is 1:1-5. By adding acid (such as oxalic acid, hydrochloric acid, or citric acid), the pH of the extract of the orthopedic tissue filler material can be stabilized in the range of 8-12, making it suitable for filling bone tissue defects.

[0013] In Traditional Chinese Medicine, cuttlefish bone is used as a calcium supplement and antacid, astringing and hemostatic, reducing acid and healing sores. In folklore, cuttlefish bone powder is commonly used to stop bleeding from wounds and significantly promote wound healing. Our research has found that high-temperature calcination of cuttlefish bone ore produces cuttlefish bone powder with excellent physical properties. Powder diffraction analysis reveals that the extract from the high-temperature calcined cuttlefish bone ore primarily contains calcium oxide, a small amount of calcium hydroxide, and calcium pyrophosphate. Elemental analysis of one set of data reveals that the calcium content of the extract from the high-temperature calcined cuttlefish bone ore is tens of times higher than the normal adult serum calcium value (31.10 (1.15-2.10) mmol / L) (values ​​in parentheses are normal human serum values, the same below), and the strontium ion content is thousands of times higher than the normal adult serum strontium value (92190.06 (10-45.00) μg / L). The extract is also rich in magnesium (1.72 (0.60-1.20) mmol / L), lithium (621.73 (<72) μg / L), and chromium (35.67 (<10) μg / L), among other osteogenic ions. High-temperature calcined cuttlefish bone mineral is very easy to dissolve and can form a stable high-calcium, high-strontium and magnesium-rich slightly alkaline environment when appropriately added to orthopedic tissue filling materials.

[0014] The present invention continues to address the problems that existing bone transplant substitute materials are difficult to achieve with good three-dimensional interconnected mesh structure, mechanical strength, degradability and osteogenic activity. The present invention uses bovine or porcine cancellous bone mineral particles, which are highly similar to the structure and composition of the mineralized cell matrix of human cancellous bone, cuttlebone bone mineral powder and calcium sulfate as the main components to construct a composite granular material with bovine or porcine cancellous bone mineral porous particles as the main structure and calcium sulfate and cuttlebone bone mineral powder as a composite coating. The goal is to maintain the ideal porous structure of bovine (porcine) cancellous bone mineral while utilizing the rapid dissolution of the calcium sulfate and cuttlebone bone mineral coating to form a slightly alkaline, high calcium, high strontium and magnesium-rich local environment that is conducive to osteogenesis. When the composite material is transplanted in vivo, it can provide space for bone repair cell adhesion and osteogenesis and has a biochemical basis for osteogenesis.

[0015] Cuttlefish bone mineral powder, calcium sulfate and a blending liquid are stirred and evenly mixed to form a coating slurry, which is then stirred and coagulated with bovine or porcine cancellous bone mineral particles and granulated to form an orthopedic tissue filling material;

[0016] Or, cuttlefish bone mineral powder, calcium sulfate and a blending liquid are stirred and evenly mixed to form a coating slurry, which is then stirred and coagulated with part of bovine or porcine cancellous bone mineral particles, and granulated to form particles with cuttlefish bone mineral powder and calcium sulfate coating on the surface. The particles with cuttlefish bone mineral powder and calcium sulfate coating on the surface are then mixed with the remaining bovine or porcine cancellous bone mineral particles to form an orthopedic tissue filling material.

[0017] Total mass of cuttlefish bone mineral powder + calcium sulfate: blending solution = 1g: 0.7-1.5mL, the blending solution is normal saline or distilled water.

[0018] The calcium sulfate is calcium sulfate hemihydrate.

[0019] The particle size of the bovine or porcine cancellous bone mineral particles is 0.2-6 mm.

[0020] The preparation method of the bovine or porcine cancellous bone mineral particles is as follows:

[0021] (1) Cut the cancellous bone of the femoral condyle of cattle or pigs into bone blocks with a thickness of 1-4 cm to obtain raw bone;

[0022] (2) Place the raw bone in distilled water and cook in a pressure cooker for 35-45 minutes, then rinse with 50-70℃ water; repeat this step 5-6 times;

[0023] (3) The raw bone treated in step (2) is dried at 80-120°C for 12-24 hours, then placed in a calcining furnace and calcined at 900-1200°C for 6-12 hours. After cooling, the bovine calcined cancellous bone mineral is obtained, which is then crushed and sieved to obtain bovine or porcine cancellous bone mineral particles. Powder diffraction analysis of the bovine (porcine) cancellous bone mineral composition reveals hydroxyapatite Ca5(P O4)6(OH).

[0024] The preparation method of the cuttlefish bone mineral powder is:

[0025] (1) Clean the cuttlefish bones with water at 50-70℃, then dry them at 80-120℃ for 12-24 hours, then remove the outer shell and take out the inner core of the cuttlefish bones;

[0026] (2) Place the cuttlebone core in a crucible, then place it in a calcining furnace and calcine at 800-1200°C for 3-6 hours. After cooling, stir to obtain uniform cuttlebone powder. Powder diffraction analysis shows that the main component of the cuttlebone powder is calcium oxide, with the remainder being calcium hydroxide and calcium pyrophosphate.

[0027] The tissue filling material uses bovine or porcine cancellous bone mineral particles as a three-dimensional skeleton material and a mixture of cuttlebone mineral powder and calcium sulfate as a degradable coating material.

[0028] Preferably, the mass ratio of calcium sulfate to bovine or porcine cancellous bone mineral particles is 1:1-8.

[0029] The beneficial effects of the present invention are: using bovine (porcine) cancellous bone mineral porous particles as the main structure and calcium sulfate and cuttlebone bone mineral powder as the coating, while maintaining the porous characteristics of bovine (porcine) cancellous bone mineral, the calcium sulfate and cuttlebone coating dissolves quickly to form a local microenvironment with high calcium content and rich in magnesium ions for osteogenic activity, so that the composite material has a biochemical basis for osteogenic activity when transplanted in vivo, while providing space for bone repair cell adhesion and osteogenic activity, and providing a material basis for the remineralization of new bone, such as a high calcium, magnesium ion-rich and alkaline environment.

[0030] The coating of the present invention can dissolve relatively quickly in a simulated body fluid dissolution experiment, forming a stable local body fluid environment with slightly alkaline (pH 8-12), high calcium 11.50-33.00 (1.15-2.10 mmol / L) (the values ​​in brackets are normal values ​​of human serum, the same below), high strontium (2100-58800 (10-45.00) ug / L), and rich magnesium 0.90-2.50 (0.60-1.20 mmol / L).

[0031] The present invention has a dissolution rate in the range of 5-55% in a simulated body fluid dissolution experiment, and the dissolution rate is achieved by regulating the mass ratio of cuttlebone mineral and calcium sulfate coating in the material.

[0032] The present invention has good calcium and phosphorus deposition in a deposition experiment in phosphorus-containing simulated body fluid; the powder diffraction component analysis of the sediment shows that it is mainly hydroxyapatite, followed by octacalcium phosphate, calcium pyrophosphate, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a diagram of the tissue filling material prepared in Example 5;

[0034] Figure 2 is the powder diffraction pattern of the tissue filling material prepared in Example 5;

[0035] Figure 3 The tissue filling material prepared in Example 5 was immersed in PBS and dissolved to form a cloud-like calcium and phosphorus deposit;

[0036] Figure 4 This is a photograph of the bovine cancellous bone plate defect model PSB filled with the tissue filling material prepared in Example 8 before immersion experiment;

[0037] Figure 5 This is a photograph of the PSB immersion experiment of the bovine cancellous bone plate defect model filled with the tissue filling material prepared in Example 8;

[0038] Figure 6 is a diagram of the tissue filling material prepared in Example 9;

[0039] Figure 7This is a picture of the tissue filling material prepared in Example 10, which was immersed in PBS and dissolved to form a cloud-like calcium and phosphorus deposition;

[0040] Figure 8 This is a graph showing the results of cell activity and cell adhesion experiments on different tissue filling materials. Green fluorescence indicates the comparison of cell adhesion, survival, and adhesion plaque formation on the materials.

[0041] Figure 9 These are photos of a two-week dissolution and deposition experiment of the material PNS prepared in Example 14;

[0042] Figure 10 This is a graph showing the results of ALP alkaline phosphatase and alizarin red staining experiments on the material prepared in Example 15. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described in detail below through specific embodiments.

[0044] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following examples, unless otherwise specified, are all conventional methods in the art.

[0045] The standard concentration ranges of total calcium, strontium, magnesium, and phosphorus in human serum are: total calcium 2-2.67 mmol / L, strontium 10-45.00 μg / L, magnesium 0.6-1.2 mmol / L, and phosphorus 0.81-1.62 mmol / L. The PBS used in the following examples has a concentration of 0.01 M and a pH of 7.4.

[0046] Example 1:

[0047] (1) Preparation of cuttlefish bone mineral powder:

[0048] Cuttlefish bones were cleaned with 60°C water and dried at 100°C for 18 hours. The outer shell was then removed and the inner cuttlefish bone core was obtained. The cuttlefish bone core was calcined at high temperature (1000°C for 4.5 hours) to completely remove organic matter. After cooling, it was stirred to obtain cuttlefish bone mineral powder. The material was sent for powder diffraction and elemental analysis. The main components of the material were calcium oxide, a small amount of calcium hydroxide, and calcium pyrophosphate. Inductively coupled plasma optical emission spectrometry (SPECTROARCOS) was used to determine the calcium, magnesium, strontium, and phosphorus contents (in wt%): calcium 62.7; magnesium 0.12; strontium 0.58; and phosphorus 0.18.

[0049] XRD diffraction composition analysis results of calcined cuttlebone powder:

[0050] CaO 84.9%

[0051] Ca (OH)2 10.2%

[0052] Ca2( P2O7) 4.9%.

[0053] Cuttlefish bone mineral powder 2.5g / 100ml normal saline solution immersed for 24 hours, pH value is about 12; Medical biochemical analyzer electrolyte biochemical analysis results:

[0054] Total calcium 13.42 mmol / L, magnesium 1.72 mmol / L, phosphorus 0.00 mmol / L.

[0055] The pH value of 2.5 g of cuttlefish bone mineral powder in 25 ml of normal saline solution immersed for 14 days is close to 13;

[0056] Results of 16 metal element analysis using ICP-MS:

[0057] Calcium 31.10 (1.15-2.10) mmol / L, magnesium 3.99 (1.13-2.09) mmol / L, iron <0.10 (4.91-9.47) mmol / L, copper 0.29 (6.30-28.35) umol / L, zinc 1.13 (65.65-126.72) umol / L, lead 15.24 (<200) ug / L, chromium 35 .67 (<10)ug / L, selenium 54.33 (100-340)ug / L, molybdenum 1.30 (<3.30)ug / L, manganese 1.17 (3.0-36)ug / L, arsenic 0 .70 (<23) ug / L, lithium 621.73 (<72) ug / L, strontium 92190.06 (10-45.00) ug / L, cobalt <0.10 (<3.0) ug / L,

[0058] Cadmium <0.10 (<5.0) ug / L;

[0059] The extract of cuttlefish bone mineral powder is rich in osteogenic active ions strontium, calcium, magnesium, lithium, and chromium, especially extremely high content of calcium and strontium ions.

[0060] (2) Preparation of bovine cancellous bone mineral granules:

[0061] Adult bovine cancellous bone was washed with hot water and cut into 2.5 cm thick blocks to obtain raw bone; the raw bone was placed in drinking water and steamed in a pressure cooker for 40 minutes, then cleaned with 60°C drinking water, and this step was repeated 6 times; the raw bone was dried in a constant temperature oven at 100°C for 18 hours, and then placed in a calcining furnace, heated at a rate of 4°C / min, and calcined at 1000°C for 8 hours, and then slowly cooled to room temperature to obtain a porous bovine calcined cancellous bone mineral scaffold; the porous bovine calcined cancellous bone mineral scaffold was crushed with a stainless steel machine, and various specifications of porous granular bovine cancellous bone mineral particles, such as 0.2-1.0, 1.0-3.0, 3.0-5.0, and 4.0-6.0 mm, were screened with a stainless steel sieve for use; the material was sent for powder diffraction and elemental analysis, and the result was hydroxyapatite. The material was sent to an inductively coupled plasma optical emission spectrometer (SPECTROARCOS) for detection of calcium, magnesium, strontium and phosphorus. The test results (in wt%) were: calcium 39.2; magnesium 0.72; strontium 0.058 and phosphorus 18.1.

[0062] Example 2:

[0063] (1) Preparation of cuttlefish bone mineral powder:

[0064] The cuttlefish bones are cleaned in 50°C water and then dried at 80°C for 24 hours. The outer shell is then removed and the inner core is taken out. The inner core is then calcined at 800°C for 6 hours to completely remove organic matter. After cooling, the cuttlefish bone powder is obtained by stirring. The powder diffraction analysis of the material reveals that the primary components are calcium oxide, followed by calcium hydroxide and calcium pyrophosphate.

[0065] (2) Preparation of bovine cancellous bone mineral granules:

[0066] Adult bovine cancellous bone was washed with hot water and cut into 1 cm thick blocks to obtain raw bone. The raw bone was then steamed in drinking water in an autoclave for 35 minutes, then rinsed with 50°C drinking water, and this process was repeated five times. The raw bone was dried in a constant temperature oven at 80°C for 24 hours, then calcined at 900°C for 12 hours in a calcining furnace at a rate of 5°C / min, then slowly cooled to room temperature to obtain a porous scaffold of calcined bovine cancellous bone mineral. The porous scaffold was crushed using a stainless steel machine and sieved using a stainless steel sieve to obtain porous bovine cancellous bone mineral particles of various sizes, such as 0.2-1.0, 1.0-3.0, 3.0-5.0, and 4.0-6.0 mm. The powder diffraction analysis of the material revealed hydroxyapatite.

[0067] Example 3:

[0068] (1) Preparation of cuttlefish bone mineral powder:

[0069] The cuttlefish bones are cleaned in 70°C water and then dried at 120°C for 12 hours. The outer shell is then removed and the inner core is taken out. The inner core is then calcined at 1200°C for 3 hours to completely remove organic matter. After cooling, the cuttlefish bone powder is obtained by stirring. Powder diffraction analysis of the material reveals that the primary components are calcium oxide, followed by calcium hydroxide and calcium pyrophosphate.

[0070] (2) Preparation of porcine cancellous bone mineral granules:

[0071] Adult porcine cancellous bone was washed with hot water and cut into 4 cm thick blocks to obtain raw bone. The raw bone was then steamed in drinking water in an autoclave for 45 minutes, then rinsed with 70°C drinking water, and this process was repeated six times. The raw bone was dried in a constant temperature oven at 120°C for 12 hours, then calcined at 1200°C for 6 hours in a calcining furnace at a rate of 2.5°C / min, then slowly cooled to room temperature to obtain a porous porcine cancellous bone mineral scaffold. The calcined porcine cancellous bone mineral scaffold was crushed using a stainless steel machine and sieved using a stainless steel sieve to obtain porous porcine cancellous bone mineral particles of various sizes, such as 0.2-1.0, 1.0-3.0, 3.0-5.0, and 4.0-6.0 mm. The powder diffraction analysis of the material revealed hydroxyapatite.

[0072] Example 4:

[0073] 2212121: Set the mass ratio of calcium sulfate / bovine cancellous bone particles to 1:1; the mass ratio of cuttlebone powder / calcium sulfate hemihydrate to 1:1; and prepare 9 g of bovine cancellous bone particles (particle size 1-3 mm). First, mix 4.5 g of cuttlebone powder and 4.5 g of calcium sulfate hemihydrate. Adjust the pH with 0.5 g of oxalic acid, which is 1 / 9 the mass of the cuttlebone powder. Add 10 ml of normal saline and stir repeatedly to form a slurry. Then, add 9 g of bovine cancellous bone particles and mix. Repeatedly squeeze and stir, then separate the particles. Dry at 95°C for 24 hours to obtain composite particles with the inner core of bovine cancellous bone particles coated with cuttlebone powder and calcium sulfate.

[0074] 2212122 (Comparison): Set the (cuttlefish bone mineral powder + calcium sulfate) / bovine cancellous bone mineral particle mass ratio to 1:1; the cuttlefish bone mineral powder / calcium sulfate hemihydrate mass ratio to 2:1, totaling 9 grams, including 6 grams of cuttlefish bone mineral powder and 3 grams of calcium sulfate hemihydrate. 0.5 grams of oxalic acid, 1 / 9 of the mass of cuttlefish bone mineral powder, was used to adjust the pH. The (cuttlefish bone mineral powder + calcium sulfate) / bovine cancellous bone mineral particle mass ratio was 1:1.5. 13.5 grams of bovine cancellous bone mineral (particle size 1-3 mm) was used. First, take 6 grams of cuttlefish bone mineral powder, 3 grams of hemihydrate calcium sulfate, and 0.5 grams of oxalic acid and mix them evenly. Add 12 milliliters of normal saline and stir repeatedly to form a slurry. Then add 13.5 grams of bovine cancellous bone mineral (particle size 1-3 mm) and mix them. After repeated squeezing and stirring, separate the particles and dry them at 95°C for 24 hours to obtain composite particles with the inner core being bovine cancellous bone mineral particles and the surface being coated with cuttlefish bone mineral powder + calcium sulfate.

[0075] Testing began at 10:36 on December 13, 2022, with 2212121. The particles were uniform, had a good texture, and had visible pores. The weight was 18.42 g. 2.5 g (W0) of the particles were immersed in 100 ml of NS. The particles remained granular in the NS, and the solution was slightly turbid. When shaken, particles floated in the NS.

[0076] Testing of 2212122 began at 10:36 on December 13, 2022. The particles were uniform, had a good texture, and visible pores. They weighed 22.62 g and produced more exfoliated powder than 2212121. 2.5 g (W0) of the particles were immersed in 100 ml of NS; the particles remained granular in the NS, and the solution was slightly turbid. When shaken, particles floated in the simulated body fluid.

[0077] A physiological saline (NS) dissolution test was conducted on days 1, 4, 7, 14, 21, and 28 of immersion, measuring electrolytes, calcium, phosphorus, and magnesium in the NS. Cation ICP-MS analysis was also performed on days 1 and 7. On days 1, 4, 7, 14, and 21, 50 ml of the NS solution was removed and replaced with 50 ml of normal saline. On day 28, the solid material was removed and dried (at 56°C for 9 hours), and the weight (W1) was measured. The dissolution rate was calculated as (W0 - W1) ÷ W0. Results: The pH value was approximately 9-12 at all immersion time points. The dissolution rates over four weeks were 46.4% and 37.2%, respectively. The dissolution rates were positively correlated with the mass ratio of cuttlebone mineral powder and calcium sulfate in the composite material. NS dissolution experiments 2212121 and 2212122 formed a stable slightly alkaline environment in NS with high calcium (13-13.68mmol / L), high strontium (3392-10218.(10-45.00)ug / L), rich magnesium (1.43-2.35 (mmol / L), and rich chromium (12.55-45.46 (<10)ug / L).

[0078] Cationic ICP-MS test results:

[0079] 2212121 Extract (1 day)

[0080] 1 Calcium 33.70 (1.15-2.10) mmol / L, 2 Magnesium 3.30 (1.13-2.09) mmol / L, 3 Iron <0.10 (4.91-9.47) mmol / L, 4 Copper <0.10 (6.30-28.35) umol / L, 5 Zinc 8.67 (65.65-126.72) umol / L, 6 Lead 4.69 (<200) ug / L, 7 Chromium 45.46 (<10) ug / L, 8 Selenium 38.13 (1 00-340) ug / L, 9 molybdenum 19.6 (<3.30) ug / L, 10 manganese 0.67 (3.0-36) ug / L, 11 arsenic <0.10 (<23) ug / L, 12 lithium 68.83 (<72) ug / L , 13 strontium 10218.75 (10-45.00) ug / L, 14 cobalt <0.10 (<3.0) ug / L, 15 cadmium <0.10 (<5.0) ug / L, 16 mercury <0.10 (<14.90) ug / L.

[0081] 2212122 Extract (1 day)

[0082] 1 Calcium 27.52 (1.15-2.10) mmol / L, 2 Magnesium 2.96 (1.13-2.09) mmol / L, 3 Iron <0.10 (4.91-9.47) mmol / L, 4 Copper <0.10 (6.30-28.35) umol / L, 5 Zinc 5.07 (65.65-126.72) umol / L, 6 Lead 2.68 (<200) ug / L, 7 Chromium 21.72 (<10) ug / L, 8 Selenium 22.36 (1 00-340) ug / L, 9 molybdenum 11.20 (<3.30) ug / L, 10 manganese 0.44 (3.0-36) ug / L, 11 arsenic <0.10 (<23) ug / L, 12 lithium 59.90 (<72) ug / L, 13 strontium 8893.58 (10-45.00) ug / L, 14 cobalt <0.10 (<3.0) ug / L, 15 cadmium <0.10 (<5.0) ug / L, 16 mercury <0.10 (<14.90) ug / L.

[0083] 2212121 Extract (7 days)

[0084] 1 Calcium 25.34 (1.15-2.10) mmol / L, 2 Magnesium 2.82 (1.13-2.09) mmol / L, 3 Iron <0.10 (4.91-9.47) mmol / L, 4 Copper <0.10 (6.30-28.35) umol / L, 5 Zinc 4.12 (65.65-126.72) umol / L, 6 Lead 2.23 (<200) ug / L, 7 Chromium 15.55 (<10) ug / L, 8 Selenium 19.51 ( 100-340) ug / L, 9 molybdenum 8.77 (<3.30) ug / L, 10 manganese 0.33 (3.0-36) ug / L, 11 arsenic <0.10 (<23) ug / L, 12 lithium 56.2 (<72) ug / L , 13 strontium 8643.96 (10-45.00) ug / L, 14 cobalt <0.10 (<3.0) ug / L, 15 cadmium <0.10 (<5.0) ug / L, 16 mercury <0.10 (<14.90) ug / L.

[0085] 2212122 Extract (7 days)

[0086] 1 Calcium 24.21 (1.15-2.10) mmol / L, 2 Magnesium 2.67 (1.13-2.09) mmol / L, 3 Iron <0.10 (4.91-9.47) mmol / L,

[0087] 4 Copper <0.10 (6.30-28.35) umol / L, 5 Zinc 3.95 (65.65-126.72) umol / L, 6 Lead 2.4 (<200) ug / L,

[0088] 7 chromium 12.55 (<10) ug / L, 8 selenium 8.27 (100-340) ug / L, 9 molybdenum 8.09 (<3.30) ug / L, 10 manganese 0.0.39 (3.0-36) ug / L, 11 arsenic <0.10 (<23) ug / L, 12 lithium 32.77 (<72) ug / L, 13 strontium 3392.07 (10-45.00) ug / L, 14 cobalt <0.10 (<3.0) ug / L, 15 cadmium <0.10 (<5.0) ug / L, 16 mercury <0.10 (<14.90) ug / L.

[0089] Biochemical test of extract from physiological saline (NS) precipitation experiment: 2212121

[0091] Day 1: pH 9-10, total calcium 13.57 mmol / L, magnesium 2.22 mmol / L, phosphorus 0.00 mmol / L;

[0092] Day 4: pH 9-10, total calcium 13.63 mmol / L, magnesium 2.35 mmol / L, phosphorus 0.04 mmol / L;

[0093] 7 days: pH 9-10, total calcium 13.68 mmol / L, magnesium 2.20 mmol / L, phosphorus 0.02 mmol / L;

[0094] 14 days: pH 9-10, total calcium 13.58 mmol / L, magnesium 2.08 mmol / L, phosphorus 0.03 mmol / L;

[0095] Day 21: pH 9-10, total calcium 13.51 mmol / L, magnesium 1.83 mmol / L, phosphorus 0.07 mmol / L;

[0096] Day 28: pH 9, total calcium 13.22 mmol / L, magnesium 1.50 mmol / L, phosphorus 0.03 mmol / L

[0097] W0: 2.5 grams W1: 1.34 grams; dissolution rate in four weeks (2.5-1.34) ÷ 2.5 = 46.4%. 2212122

[0099] Day 1: pH 10, total calcium 13.59 mmol / L, magnesium 2.12 mmol / L, phosphorus 0.06 mmol / L;

[0100] Day 4: pH 10, total calcium 13.62 mmol / L, magnesium 2.17 mmol / L, phosphorus 0.06 mmol / L;

[0101] 7 days: pH 10, total calcium 13.60 mmol / L, magnesium 1.88 mmol / L, phosphorus 0.01 mmol / L;

[0102] 14 days: pH 10, total calcium 13.50 mmol / L, magnesium 1.71 mmol / L, phosphorus 0.06 mmol / L;

[0103] Day 21: pH 9-10, total calcium 13.49 mmol / L, magnesium 1.60 mmol / L, phosphorus 0.05 mmol / L;

[0104] Day 28: pH 9-10, total calcium 13.23 mmol / L, magnesium 1.43 mmol / L, phosphorus 0.03 mmol / L;

[0105] W0: 2.5 grams W1: 1.57 grams; dissolution rate in four weeks (2.5-1.57) ÷ 2.5 = 37.2%.

[0106] Example 5:

[0107] 2212173: Set the calcium sulfate hemihydrate / bovine cancellous bone mineral granules mass ratio to 4:9. Set the cuttlebone mineral powder / calcium sulfate hemihydrate mass ratio to 3:4. Prepare 4.5g of cuttlebone mineral powder, 6g of calcium sulfate hemihydrate, and 0.25g of oxalic acid (1 / 18th the mass of the cuttlebone mineral powder). Add 13.5g of bovine cancellous bone mineral granules (particle size 3-5mm) to 10ml of distilled water, stirring repeatedly to form a slurry. Add 13.5g of bovine cancellous bone mineral granules and stir to form a concrete-like mixture. Particles are then separated into mixed granules consisting primarily of bovine cancellous bone mineral granules with a cuttlebone mineral powder / calcium sulfate hemihydrate coating. Dry at 27°C for 48 hours; the granules weigh 23.19g and have excellent texture. Figure 1 , send powder diffraction ( Figure 2 ).

[0108] NS immersion dissolution experiment: 2.5 g material / 100 ml normal saline solution, calcium, magnesium and phosphorus tests were performed using a medical automatic biochemical analyzer on days 1, 4, 7, 14, 21, 28, 35 and 42. On days 4, 7, 14, 21, 28 and 35, 50 ml of the experimental solution was removed and replaced with 50 ml of normal saline solution. On day 42 of immersion, the stent was removed and dried for 24 hours, and the particle weight (W1) was weighed to calculate the dissolution rate.

[0109] PBS immersion dissolution experiment: Take 5 grams of 2212173 particles and 200 ml of PBS. After 2 days, replace half of the experimental solution with new PBS solution. Perform PBS solution sedimentation experiments and calcium, magnesium, and phosphorus tests on the 2nd and 5th days to observe the calcium and phosphorus deposition. After removing the particles, dilute the solution with distilled water and reprecipitate, then take the supernatant. Repeat three times, dry the flocculent sediment at 55°C for 24 hours, and send it for powder diffraction.

[0110] Results: The pH value of all saline solutions during the experiment was approximately 7.5-11. The 6-week solution reduction rate was 43.6%. During the first three weeks of observation, a stable microenvironment with high calcium content (>8 mmol / L) and high magnesium content (>0.9 mmol / L) was formed in the 2212173 saline solution. After immersion in PBS phosphate buffer, the solution quickly showed typical phosphate flocculent deposition ( Figure 3 ), it spreads out in the solution in a cloud-like manner when gently shaken, and slowly sinks after standing. The sediment is mainly hydroxyapatite.

[0111] 2212173 Powder diffraction composition test results of mixed particles with bovine cancellous bone mineral particles as the main body and cuttlebone bone mineral powder / hemihydrate calcium sulfate coating:

[0112] Ca 9.74 ( P O4)6( OH ) 2.08 72.6%

[0113] Ca S O4·2 H2O 9.5%

[0114] CaS O4 14.1%

[0115] Ca ( OH )2 3.8%.

[0116] 2212173 Powder diffraction test results of sediments from a five-day PBS dissolution and precipitation experiment:

[0117] Ca 10.042 ( P O4) 5.952 ( OH ) 2.292 92.5%

[0118] Ca (OH)2 4.9%

[0119] Ca S O4( H2O )2 2.6%.

[0120] 2212173 NS immersion for 1 day: pH 11, total calcium 13.50 mmol / L, magnesium 2.21 mmol / L, phosphorus 0.01 mmol / L;

[0121] Day 4: pH 11, total calcium 13.59 mmol / L, magnesium 2.10 mmol / L, phosphorus 0.01 mmol / L;

[0122] pH 11, total calcium 13.55 mmol / L, magnesium 2.01 mmol / L, phosphorus 0.04 mmol / L at 7 days;

[0123] Day 14: pH 10, total calcium 13.29 mmol / L, magnesium 1.70 mmol / L, phosphorus 0.03 mmol / L;

[0124] On day 21, the pH was 10, total calcium 12.88 mmol / L, magnesium 1.22 mmol / L, and phosphorus 0.03 mmol / L;

[0125] On day 28, the pH was 9.0, total calcium 9.51 mmol / L, magnesium 0.01 mmol / L, and phosphorus 0.01 mmol / L;

[0126] On day 35, the pH was 9, total calcium 5.23 mmol / L, magnesium 0.01 mmol / L, and phosphorus 0.01 mmol / L;

[0127] On day 42, the pH was 7.5, total calcium 3.14 mmol / L, magnesium 0.01 mmol / L, and phosphorus 0.01 mmol / L;

[0128] W0: 2.5 g W1: 1.41 g; dissolution rate = 43.6%.

[0129] 2212173PBS dissolution experiment

[0130] pH 10, total calcium 0.23 mmol / L, magnesium 0.00 mmol / L, phosphorus 2.23 mmol / L on day 2;

[0131] Day 5: pH 9.0, total calcium 3.28 mmol / L, magnesium 0.00 mmol / L, phosphorus 0.00 mmol / L.

[0132] Example 6:

[0133] 2302051 Cuttlefish bone mineral powder / calcium sulfate hemihydrate mass ratio 1:2; 9 grams of cuttlefish bone mineral powder, 18 grams of calcium sulfate hemihydrate; 28 grams of bovine cancellous bone mineral particles (particle size 3-4 mm); cuttlefish bone mineral powder / calcium sulfate hemihydrate 27 grams, add 20 milliliters of normal saline and 1.29 grams of oxalic acid, after repeated stirring, add bovine cancellous bone mineral particles, stir into a concrete sample, and then granulate. Dry in a constant temperature oven at 35°C for 24 hours, and take out 57.76 grams of particles with excellent particle quality, and send for powder diffraction.

[0134] NS saline dissolution and precipitation experiment: the solid-liquid ratio of material to saline is: 100 ml NS / 2.5 g sample. After immersion for 1 week, the supernatant is taken and the calcium, phosphorus, magnesium and pH values ​​are detected using a medical biochemical analyzer.

[0135] PNS dissolution and immersion experiment: The solid-to-liquid ratio of materials and PNS (phosphate-containing saline (PNS) equivalent to the average human serum phosphorus content, i.e., 61 ml of 0.01 M PBS solution added to 500 ml of saline) was: 100 ml of PNS solution / 5 g of sample. The supernatant was taken after immersion for 1, 2, 3, 4, and 5 weeks, and the calcium, phosphorus, magnesium, and pH values ​​were detected using a BECMAN COULTEY AU5800 medical biochemical analyzer. 50 ml of PNS solution was added after 1, 2, 3, and 4 weeks.

[0136] Results: NS saline solution produced a high calcium (total calcium 13.19 mmol / L) and magnesium-rich (magnesium 1.53 mmol / L) environment after one week of immersion. The pH of the PNS sedimentation experiment was approximately 9-8 at all immersion time points. Cloudy precipitates were observed early in the PNS immersion experiment and gradually increased throughout the observation period, with a 23.4% immersion rate and a 21.4% deposition rate after five weeks.

[0137] 2302051 powder diffraction analysis:

[0138] Ca 9.74 ( P O4)6( OH ) 2.0850.6%

[0139] CaS O4 39.1%

[0140] Ca S O4·2 H2O 7.8%

[0141] Ca (OH)2 1.9%

[0142] CaO 5.1%

[0143] Mg ( H2P O2)2( H2O )6 1.6%.

[0144] NS 1-week pH value was 9.0, total calcium 13.19 mmol / L, magnesium 1.53 mmol / L, and phosphorus 0.00 mmol / L.

[0145] PNS pH 1 week: 9.0, total calcium: 13.16 mmol / L, magnesium: 1.49 mmol / L, phosphorus: 0.54 mmol / L;

[0146] PNS pH 9.0, total calcium 13.35 mmol / L, magnesium 2.15 mmol / L, phosphorus 0.47 mmol / L at 2 weeks;

[0147] PNS pH at 3 weeks was 8.5, total calcium 13.22 mmol / L, magnesium 2.01 mmol / L, phosphorus 0.46 mmol / L;

[0148] At 4 weeks, the pH of the PNS was 8.5, total calcium was 13.22 mmol / L, magnesium was 2.09 mmol / L, and phosphorus was 0.20 mmol / L;

[0149] PNS pH 5 weeks: 8, total calcium 13.15 mmol / L, magnesium 1.97 mmol / L, phosphorus 0.39 mmol / L;

[0150] The dissolution rate is (5.0-3.83) ÷ 5 = 23.4%, and the deposition rate is 1.07 ÷ 5 = 21.4%.

[0151] Example 7:

[0152] 2302121: (Cuttlefish bone powder + calcium sulfate hemihydrate) / bovine cancellous bone granules 3:4; cuttlefish bone powder / calcium sulfate hemihydrate mass ratio 1:1. Prepare 6 grams of cuttlefish bone powder, 6 grams of calcium sulfate hemihydrate, and 16 grams of bovine cancellous bone granules (particle size 1-3 mm). Stir 10 ml of calcium sulfate and normal saline, then add the cuttlefish bone powder, stir and squeeze until the mixture reaches a mortar consistency. Add the bovine cancellous bone granules, stir until the mixture reaches a concrete-like consistency, and then granulate to form granules coated with cuttlefish bone powder and calcium sulfate. Dry at 35°C for 24 hours. 2302121 weighs 29.35 grams.

[0153] 2302122: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone granules (1:2, mass ratio of cuttlefish bone powder to calcium sulfate hemihydrate: 1:1). 4 g cuttlefish bone powder, 4 g calcium sulfate hemihydrate; 16 g bovine cancellous bone granules (particle size 2-4 mm). Stir the calcium sulfate with 4 ml of saline solution, then add the cuttlefish bone powder. Add 5 ml of saline solution and mix to form a slurry. Add the bovine cancellous bone granules and mix to form a concrete-like slurry. Then, separate the granules to form granules coated with cuttlefish bone powder and calcium sulfate. Dry at 35°C for 24 hours. 2302122 weighs 24.55 g.

[0154] 2302123: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules (ratio approximately 3:8). Take one-fourth the amount of dry 2302121 and add 4g of bovine cancellous bone mineral granules (particle size 1-3 mm) to make 2302123.

[0155] 2302124: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules about 1:4: Take one-fourth of the mass of 2302122, add 4 grams of bovine cancellous bone mineral granules (particle size 2-4 mm) and mix well to obtain 2302124.

[0156] 2302125: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules about 1:4: Take one-fourth of the mass of dry 2302121, add 8 grams of bovine cancellous bone mineral granules (diameter 1-3 mm) and mix well to obtain 2302125.

[0157] 2302126: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules about 1:6: Take one-fourth of the mass of 2302122, add 8 grams of bovine cancellous bone mineral granules (diameter 2-4 mm) and mix well to obtain 2302126.

[0158] 2302127: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules about 1:8: Take one-eighth of the mass of 2302121, add 10 grams of bovine cancellous bone mineral granules (diameter 2-4 mm) and mix well to obtain 2302127.

[0159] The bovine cancellous bone mineral particles of 2302121 - 2302127 and the control group were sent for cell culture, and 2302121 was sent for powder diffraction.

[0160] NS normal saline dissolution and deposition experiment: For the materials (2302121\2302122\2302123), the solid - liquid ratio with normal saline was 0.1 g / 1.5 mL, that is, 30 mL of NS solution / 2 g of sample. At time points such as 24, 72, 168, and 336 hours, the supernatant was taken and the calcium, phosphorus, magnesium ions and pH value were detected using a medical biochemical analyzer. And 30 mL of NS solution was added at time points such as 24 and 72 hours; 60 mL of NS solution was added at 168 hours; the particles were taken out at the end of the 336 - hour [2 - week] experiment; dried at 95°C for 24 hours, weighed as W1, and the dissolution rate was calculated.

[0161] Results: At all immersion time points, the pH value was about 11 - 12. The two - week dissolution rates were 32.5%, 15%, and 9% respectively. The dissolution rate was positively correlated with the mass ratio of (cuttlefish bone + calcium sulfate) in the composite material; it was observed that in two weeks, 2302121\2302122\2302123 could form a stable micro - environment with high calcium (>8 mmol / L) and rich magnesium (>0.9 mmol / L) in physiological saline.

[0162] Cell culture with material extract: Through cell viability and cell adhesion experiments, the order of material groups with better cell viability and biocompatibility (from smallest to largest activity) was: HA control group <2302126> = 2302127 <2302124>=2302125 <2302122> = 2302123 <2302121> (attached Figure 8 ) <00,00359>Powder diffraction of 2302121

[0164] Ca5(PO4)3(OH) 47.1%

[0165] CaSO4 40.3%

[0166] Ca(OH)2 6.2%

[0167] CaO 2.3%

[0168] Ca(SO4)(H2O) 0.5 4.1%.

[0169] Example 8:

[0170] 2302128: Set the mass ratio of calcium sulfate hemihydrate to bovine cancellous bone granules at 1:1, and the mass ratio of cuttlebone powder to calcium sulfate hemihydrate at 3:4. Prepare 9 grams of cuttlebone powder, 12 grams of sulfuric acid hemihydrate, 12 grams of bovine cancellous bone granules (1-3 mm in diameter), and 9 grams of bovine cancellous bone granules smaller than 0.5 mm. Add 9 grams each of calcium sulfate and cuttlebone powder to 15 ml of saline solution, stirring and extruding repeatedly until the mixture reaches a mortar consistency. Then, add 21 grams of bovine cancellous bone granules, stirring and extruding until the mixture is coated with cuttlebone powder and calcium sulfate. Then, add 3 grams of calcium sulfate and 1.5 ml of saline solution, stirring until the mixture becomes a concrete-like consistency.

[0171] Hard tissue defect model filling experiment and PBS dissolution and deposition experiment:

[0172] Material 2302128 was used to fill a full-thickness bovine cancellous bone defect model consisting of two 1.75 cm thick bovine cancellous bone plates (3.3 cm in diameter). The plates, filled with a "concrete" of cuttlebone mineral powder, calcium sulfate, and bovine cancellous bone mineral particles, were immediately immersed in a 500 ml beaker of PBS for five days of dissolution and sedimentation. Photos were taken before and after the dissolution and sedimentation experiment. The cuttlebone mineral powder, calcium sulfate, and bovine cancellous bone mineral particle concrete exhibited a typical flocculent deposit in the PBS solution. At the end of the dissolution experiment, the concrete's surface "mud paste" significantly dissolved, but the bone defects remained well-filled and the fillings maintained good strength. Under a magnifying glass, the porous structure of the bovine cancellous bone mineral was revealed ( Figure 4 , Figure 5 ).

[0173] Example 9:

[0174] 2302201: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules 1:2, cuttlefish bone mineral powder / calcium sulfate hemihydrate mass ratio 1:2; i.e., cuttlefish bone mineral powder 4 g, calcium sulfate hemihydrate 8 g; bovine cancellous bone mineral granules (diameter 0.35-1 mm) 24 g; take 8 g of calcium sulfate, add 4 ml of normal saline and stir, add cuttlefish bone mineral powder and stir, add 4 ml of normal saline and stir and squeeze to the viscosity of mud, then add bovine cancellous bone mineral granules, stir and squeeze to concrete-like consistency, and then granulate; dry at 35°C for 24 hours, weigh 230201 and weigh 44.79 g, the particles are relatively uniform, with a small amount of powder.

[0175] 2302202: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules 1:4; take one-sixth of the amount of dry 230201, i.e. 7.465 g, add 4 g of bovine cancellous bone mineral granules (diameter 1-3 mm) and mix well to obtain 230202.

[0176] 2302203: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules 1:8; take one-sixth of the mass of dry 2302201, i.e. 7.465g, add 12g bovine cancellous bone mineral granules (diameter 1-3mm) and mix well to obtain 2302203. See the photo of 2302203 for details. Figure 6 , the bovine cancellous bone mineral particles with cuttlebone bone mineral powder + calcium sulfate coating and the bovine cancellous bone mineral particles without coating are clearly visible.

[0177] 2302204: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules 1:16; take one twelfth of the mass of dry 2302201, i.e. 3.7325 g, add 14 g bovine cancellous bone mineral granules (diameter 0.35-1 mm), and mix thoroughly to obtain 2302204.

[0178] 2302205: (Cuttlefish bone mineral powder + calcium sulfate hemihydrate) / bovine cancellous bone mineral granules 1:32 Take one twenty-fourth of the mass of dry 2302201, i.e. 1.86625 grams, add 15 grams of bovine cancellous bone mineral granules (diameter 0.35-1 mm) and mix well to obtain 2302205.

[0179] NS Simulated Body Fluid [Normal Saline] Extraction Experiment: Scaffold material was mixed with simulated body fluid (normal saline) at a solid-liquid ratio of 0.2 g / 1 ml. The supernatant was aspirated with a pipette at 6 hours, 12 hours, 24 hours, 72 hours, and 168 hours, and promptly analyzed for sodium, potassium, chloride, calcium, magnesium, and phosphorus using a medical biochemical analyzer. Results: During the experiment, 2302201, 2302202, 2302303, and 2302204 demonstrated sustained and stable calcium and magnesium ion release at all observation times, creating a high-calcium and magnesium-rich environment. Early in the immersion period in the simulated body fluid, such as at 6, 12, 24, and 72 hours, the scaffold material reached elevated levels, reaching five times the average total calcium concentration in human serum, and the magnesium concentration was greater than the average human serum magnesium concentration.

[0180] PNS simulated body fluid [Physiological saline (PNS) containing phosphorus equivalent to the average value of human serum phosphorus, i.e., 61 ml of 0.01 molar PBS solution plus physiological saline to 500 ml] dissolution and precipitation experiment: the experiment was started at a solid-liquid ratio of 0.2 g / 1 ml of material to simulated body fluid (physiological saline), i.e., 4 g of sample per 20 ml of PNS solution. Electrolyte analysis was performed at time points such as 3, 6, 9, 12, and 15 days. 20 ml of PNS solution was added at time points such as 3, 6, 9, and 12 days respectively. The granular material was taken out on the 15th day and dried in a constant temperature oven at 95°C for 24 hours. The dissolution rate was calculated. It was observed that in the early stages of the PNS simulated body fluid experiment, such as on the 3rd and 6th days, there was a typical calcium-phosphorus cloud-like deposition (see Figure 3), after which the typical calcium-phosphorus cloud-like deposits gradually thickened at each time period. Simultaneously, the calcium and magnesium ion concentrations in the PNS gradually decreased, indicating that the high calcium and magnesium-rich environment in the immersion solution provided the biochemical basis for the redeposition of calcium and phosphate.

[0181] PNS simulated body fluid dissolution and deposition experiment:

[0182] 2302201 PNS3T: total calcium 13.44 (2-2.67 mmol / L), magnesium 2.24 (0.6-1.2 mmol / L), phosphorus 0.03 (0.81-1.62 mmol / L);

[0183] 2302201 PNS6T: total calcium 13.48 (2-2.67 mmol / L), magnesium 2.22 (0.6-1.2 mmol / L), phosphorus 0.51 (0.81-1.62 mmol / L);

[0184] 2302201 PNS9T: total calcium 12.37 (2-2.67 mmol / L), magnesium 2.29 (0.6-1.2 mmol / L), phosphorus 0.44 (0.81-1.62 mmol / L);

[0185] 2302201 PNS12T: total calcium 13.34 (2-2.67 mmol / L), magnesium 2.07 (0.6-1.2 mmol / L), phosphorus 0.38 (0.81-1.62 mmol / L);

[0186] 2302201 PNS15T: Total calcium 12.54 (2-2.67 mmol / L), magnesium 1.02 (0.6-1.2 mmol / L), phosphorus 0.38 (0.81-1.62 mmol / L)

[0187] The particle weight after the PNS dissolution test was 2.25 g; the dissolution rate was (4-2.75) ÷ 4 = 31.25%; the powder deposition after PNS was 0.97 g.

[0188] 2302202PNS3T: total calcium 13.47 (2-2.67 mmol / L), magnesium 2.28 (0.6-1.2 mmol / L), phosphorus 0.04 (0.81-1.62 mmol / L);

[0189] 22302202PNS6T: total calcium 13.43 (2-2.67 mmol / L), magnesium 2.28 (0.6-1.2 mmol / L), phosphorus 0.58 (0.81-1.62 mmol / L);

[0190] 2302202PNS9T: total calcium 13.22 (2-2.67 mmol / L), magnesium 2.10 (0.6-1.2 mmol / L), phosphorus 0.33 (0.81-1.62 mmol / L);

[0191] 2302202PNS12T: total calcium 12.54 (2-2.67 mmol / L), magnesium 1.02 (0.6-1.2 mmol / L), phosphorus 0.38 (0.81-1.62 mmol / L);

[0192] 2302202PNS15T: Total calcium 9.11 (2-2.67mmol / L), magnesium 0 (0.6-1.2mmol / L), phosphorus 0 (0.81-1.62mmol / L);

[0193] The particle weight after the PNS dissolution test was 3.06 g; the dissolution rate was (4-3.06) ÷ 4 = 23.5%; the powder deposition after PNS was 0.78 g.

[0194] 2302203PNS3T: total calcium 13.43 (2-2.67 mmol / L), magnesium 2.25 (0.6-1.2 mmol / L), phosphorus 0.05 (0.81-1.62 mmol / L);

[0195] 2302203PNS6T: total calcium 13.37 (2-2.67 mmol / L), magnesium 2.08 (0.6-1.2 mmol / L), phosphorus 0.57 (0.81-1.62 mmol / L);

[0196] 2302203PNS9T: total calcium 13.16 (2-2.67 mmol / L), magnesium 1.91 (0.6-1.2 mmol / L), phosphorus 0.45 (0.81-1.62 mmol / L);

[0197] 2302203PNS12T: total calcium 13.00 (2-2.67 mmol / L), magnesium 1.69 (0.6-1.2 mmol / L), phosphorus 0.32 (0.81-1.62 mmol / L);

[0198] 2302203PNS15T: total calcium 12.85 (2-2.67 mmol / L), magnesium 1.21 (0.6-1.2 mmol / L), phosphorus 0.53 (0.81-1.62 mmol / L);

[0199] After the PNS dissolution test, the granules weighed 3.56 grams; the dissolution rate was (4-3.56) ÷ 4 = 11%.

[0200] 2302204PNS3T: total calcium 13.50 (2-2.67 mmol / L), magnesium 2.26 (0.6-1.2 mmol / L), phosphorus 0.06 (0.81-1.62 mmol / L);

[0201] 2302204PNS6T: total calcium 13.26 (2-2.67 mmol / L), magnesium 1.94 (0.6-1.2 mmol / L), phosphorus 0.58 (0.81-1.62 mmol / L);

[0202] 2302204PNS9T: total calcium 12.51 (2-2.67 mmol / L), magnesium 1.01 (0.6-1.2 mmol / L), phosphorus 0.48 (0.81-1.62 mmol / L);

[0203] 2302204PNS12T: total calcium 10.20 (2-2.67mmol / L), magnesium 0.04 (0.6-1.2mmol / L), phosphorus 0.22 (0.81-1.62mmol / L);

[0204] 2302204PNS15T: total calcium 8.87 (2-2.67 mmol / L), magnesium 0.00 (0.6-1.2 mmol / L), phosphorus 0.73 (0.81-1.62 mmol / L);

[0205] The granules weighed 3.75 g after PNS; the solubility reduction rate was (4-3.75) ÷ 4 = 6.25%.

[0206] 2302205PNS3T: total calcium 13.45 (2-2.67 mmol / L), magnesium 2.08 (0.6-1.2 mmol / L), phosphorus 0.07 (0.81-1.62 mmol / L);

[0207] 2302205PNS6T: total calcium 12.7 (2-2.67 mmol / L), magnesium 1.07 (0.6-1.2 mmol / L), phosphorus 1.05 (0.81-1.62 mmol / L);

[0208] 2302205PNS9T: total calcium 3.65 (2-2.67 mmol / L), magnesium 0.02 (0.6-1.2 mmol / L), phosphorus 1.00 (0.81-1.62 mmol / L);

[0209] 2302205PNS12T: total calcium 1.04 (2-2.67 mmol / L), magnesium 0.10 (0.6-1.2 mmol / L), phosphorus 0.38 (0.81-1.62 mmol / L);

[0210] 2302205PNS15T: total calcium 0.90 (2-2.67 mmol / L), magnesium 0.21 (0.6-1.2 mmol / L), phosphorus 0.61 (0.81-1.62 mmol / L);

[0211] The weight of the particles after PNS was 3.87 g; the dissolution rate was (4-3.87) ÷ 4 = 3.25%.

[0212] Example 10:

[0213] 2302271: Calcium sulfate hemihydrate / bovine cancellous bone granules 2:3; cuttlebone powder / calcium sulfate hemihydrate 1:8; i.e., 2g cuttlebone powder, 16g calcium sulfate hemihydrate, and 24g bovine cancellous bone granules (0.35-1mm diameter). Calcium sulfate was mixed with 8ml of saline, stirred and extruded to a slurry consistency. Then, cuttlebone powder was added, stirred, and 6ml of saline was added, stirred and extruded to a slurry consistency. Then, bovine cancellous bone granules were added, stirred, extruded, and granulated into mixed granules consisting primarily of bovine cancellous bone granules with cuttlebone powder and calcium sulfate slurry on the surface. The mixture was allowed to stand at 35°C for 24 hours, followed by drying at 95°C for 1180 minutes. 230271 weighed 41.8g, showing relatively uniform granules with a small amount of powder. The cuttlebone powder / total granule mass was 1 / 21.

[0214] 2302272: Calcium sulfate hemihydrate / bovine cancellous bone granules 1:3; cuttlebone mineral powder / calcium sulfate hemihydrate 1:8; take one-quarter (10.45g) of 2302271: containing 0.5g of cuttlebone mineral powder, 4g of sulfate hemihydrate, and 6g of bovine cancellous bone granules (0.35-1mm diameter); add 6g of bovine cancellous bone granules (0.35-1mm diameter) and mix thoroughly; dry at 35°C for 24 hours. Weigh the granules, which are relatively uniform and contain a small amount of powder. The cuttlebone mineral powder / total granule mass = 1 / 33.

[0215] 2302273: Calcium sulfate hemihydrate / bovine cancellous bone granules 1:6; cuttlebone powder / calcium sulfate hemihydrate 1:8. Take one-quarter (10.45 g) of 2302271 (containing 4 g of calcium sulfate, 0.5 g of cuttlebone powder, and 6 g of bovine cancellous bone granules), add 18 g of bovine cancellous bone granules (0.35-1 mm diameter), and mix thoroughly. Dry at 35°C for 24 hours to obtain relatively uniform granules with minimal powder. The cuttlebone powder / total granule mass is 1 / 57.

[0216] 2302274: Calcium sulfate hemihydrate / bovine cancellous bone granules 1:12; cuttlebone powder / calcium sulfate hemihydrate 1:8. Take one-eighth (5.225g) of 2302271 (containing 0.25g of cuttlebone powder, 2g of calcium sulfate hemihydrate, and 3g of bovine cancellous bone granules (0.35-1mm diameter), add 21g of bovine cancellous bone granules (0.35-1mm diameter), and mix thoroughly. Dry at 35°C for 24 hours to obtain relatively uniform granules with minimal powder. The cuttlebone powder / total granule mass is 1 / 105.

[0093] NS solution dissolution and precipitation experiment: The dissolution and precipitation experiment was started at a solid-to-liquid ratio of 4 g / 100 ml of the material to simulated body fluid (normal saline). 50 ml of the supernatant was aspirated at each time point on days 3, 6, 9, 12, 15, and 18, and sodium, potassium, chloride, calcium, magnesium, and phosphorus were added simultaneously. At the same time, 50 ml of simulated body fluid was added. On day 21, the pellets were removed and dried at 95°C for 24 hours before powder diffraction and elemental analysis.

[0217] PNS liquid dissolution and precipitation experiment: start the dissolution and precipitation experiment according to the solid-liquid ratio of material to simulated body fluid (PNS) of 0.1 g / 1 ml, i.e. 4 g / 40 ml. At each time point on days 3, 6, 9, 12, 15, and 18, aspirate 1 ml of supernatant with a pipette and add sodium, potassium, chloride, calcium, magnesium, phosphorus, etc. at the same time. At the same time, add simulated body fluid (40 ml / 3 days). Take out the particles on day 18, dry the supernatant, dry the particles and sedimentation liquid (dry at 95℃ for 24 hours), and then do powder diffraction.

[0218] Results: Dissolution was visible in the NS immersion experiment. Biochemical analysis of the immersion fluids of 2302271-2302273 showed that a high calcium and magnesium-rich environment could be formed (2302272: total calcium 11.04-13.22 mmol / L, magnesium 0.99-1.34 mmol / L; 2302273: total calcium 10.05-13.29 mmol / L, magnesium 0.91-1.79 mmol / L). The effect of 2302274 was poor (2302274: total calcium 0.8-12.42 mmol / L, magnesium 0.07-0.98 mmol / L). Powder diffraction analysis showed that 2302271 was Ca 10.042 ( P O4) 5.952 ( OH ) 2.292 53.4%, Ca S O442.7%, Ca (SO4) (H2O) 0.5 3.8%. In the PNS liquid dissolution and precipitation experiment, typical cloud-like calcium and phosphorus precipitation can be seen in the early stage of the experiment, and the precipitation gradually increases. Powder diffraction analysis shows that the precipitation of 2302271 is Ca (S O4)(H2O) 0.583 20.7%; Ca 10.042 ( P O4) 5.952 ( OH ) 2.29279.3%.

[0219] Example 11:

[0220] 2304101: calcium sulfate / bovine cancellous bone mineral particles = 1:2; cuttlebone / calcium sulfate = 1 / 1; take 6 grams of cuttlebone bone mineral powder, add 10 ml of distilled water and 0.5 grams of oxalic acid to adjust the pH value to 10-11; add 6 grams of calcium sulfate, stir and squeeze to form putty, add 12 grams of bovine cancellous bone mineral particles with a particle size of 2-4 mm, stir and squeeze thoroughly to form a concrete-like state, then granulate, let it stand at 35°C for 24 hours; dry at 95°C for 24 hours to obtain 24.72 grams of 2304101 material (with a lot of falling powder).

[0221] 2304102: Take one-sixth of the total mass of 2304101, i.e., 4.12 (containing 2 g HA, 1 g cuttlebone mineral powder, and 1 g calcium sulfate; set the calcium sulfate / HA ratio to 1 / 4), and mix with 2 g bovine cancellous bone mineral powder (2-4 mm in size) to obtain 2304102.

[0222] 2304103: Take one-twelfth of the total mass of 2304101, or 2.06 grams, containing 1 gram of HA, 0.5 grams of cuttlefish bone mineral powder, and 0.5 grams of calcium sulfate; set the target of calcium sulfate / HA = 1 / 8, and take 3 grams of bovine cancellous bone mineral with a particle size of 2-4 mm and mix it to obtain 2304103.

[0223] 2304101 sent powder diffraction analysis, each material simulated body fluid (normal saline) dissolution and deposition experiments and PBS dissolution and deposition experiments.

[0224] Dissolution and sedimentation experiment in simulated body fluid (normal saline): According to the solid-liquid ratio of material to simulated body fluid (normal saline) of 0.1 g / 1.5 ml, that is, 30 ml of NS solution / 2 g of sample, the supernatant was collected at 24, 72, 168, and 336 hours, and the calcium, phosphorus, and magnesium ions were detected by medical biochemical analyzer, and the pH value was tested with test paper; 30 ml of NS solution was added at 24 and 72 hours, and 60 ml of NS solution was added at 168 hours; the particles were removed at the end of the experiment at 336 hours (2 weeks); dried at 95 for 24 hours, and the dissolution rate was calculated.

[0225] The results of physiological saline dissolution and deposition experiments showed that the pH was approximately 10-11 at all immersion time points. A high-calcium (13.67-8 (2-2.67 mmol / L), or 4-7 times the average human serum total calcium) and magnesium-rich (0.9-2.49 (0.6-1.2 mmol / L), > the average human serum magnesium) environment was established early in the dissolution process. Dissolution rates were 34%, 16%, and 7% over two weeks, respectively. These rates were positively correlated with the mass ratio of cuttlefish bone to calcium sulfate coating in the composite material.

[0226] PBS Dissolution and Deposition Experiment: According to the solid-liquid ratio of the material to the simulated body fluid (normal saline) of 0.1 g / 1 mL, that is, 60 mL of PSB solution / 2 g of sample, the supernatant was taken at time points such as 24, 72, 168, and 336 hours, and calcium, phosphorus, magnesium and other ions were detected with a medical biochemical analyzer, and the pH value was tested with test paper. And 60 mL of PBS solution was added at the 24-hour and 72-hour time points; 120 mL of PBS solution was added at 168 hours (1 week), and the particles were taken out at the end of the experiment when the dissolution and deposition reached 336 hours (2 weeks), dried at 95°C for 24 hours, and the dissolution rate was calculated; obvious flocculent deposits were found at 24 hours; after adding 60 mL of PBS solution at 72 hours, the flocculent deposits increased significantly ( Figure 7 ); finally, it was found that the flocculent deposits were <2304101><2304102>2304103. After the dissolution and deposition experiment, the particles were taken out. The liquids of the 3 dissolution experiments were concentrated and deposited, and the supernatant was carefully aspirated. The particles and the solution containing the deposits were dried in an incubator at 95°C for 24 hours, and the deposition rate was calculated; the particles and the precipitate were respectively subjected to powder diffraction elemental analysis. Results: The pH value was about 9-11 at all immersion time nodes. The dissolution rates for two weeks were 35.5%, 21%, and 12% respectively, and the dissolution rate was positively correlated with the mass ratio of (cuttlefish bone + calcium sulfate) in the composite material. The powder diffraction component analysis of the total deposits for two weeks showed that the calcium and phosphorus deposits were hydroxyapatite, and the total deposition rate for two weeks was 1.08÷6×0.722 = 11.4%.

[0227] [[ID=⑤]]Example 12:[[ID=⑥]] [[ID=⑦]]

[0228] [[ID=⑧]]2304121: Calcium sulfate / HA = 1 / ②; cuttlefish bone / calcium sulfate = 1 / 1; Take 6 g of cuttlefish bone mineral powder, add 10 mL of distilled water and 0.5 g of oxalic acid to detect the pH value of 10-11; add 6 g of calcium sulfate, stir and extrude to mix into a putty, add 12 g of bovine cancellous bone mineral particles with a particle size of 2-4 mm, stir and extrude to mix into a concrete shape and then extrude into granules, and let the material stand at 35°C; dry at 95°C for 24 hours to obtain 24.72 g of 2304121 material.[[ID=⑨]] [[ID=⑩]]

[0229] [[ID=⑪]]2304122: Take one-sixth of the total mass of 2304121, that is, containing 2 g of HA, 1 g of cuttlefish bone mineral powder, and 1 g of calcium sulfate; set calcium sulfate / HA = 1 / 4, and take 2 g of bovine cancellous bone mineral particles with a particle size of 2-4 mm and mix them to obtain it.[[ID=⑫]] [[ID=⑬]]

[0230] [[ID=⑭]]2304123: Take one-twelfth of the total mass of 2304121, that is, containing 1 g of HA, 0.5 g of cuttlefish bone mineral powder, and 0.5 g of calcium sulfate; set calcium sulfate / HA = 1 / 8, and take 3 g of bovine cancellous bone mineral particles with a particle size of 2-4 mm and mix them to obtain it.[[ID=⑮]] [[ID=⑯]]

[0231] 2304124: Take one twenty-fourth of the total mass of 2304121, which contains 0.5 g HA, 0.25 g cuttlefish bone mineral powder, and 0.25 g calcium sulfate; set (calcium sulfate + cuttlefish bone mineral powder) / HA = 1 / 16, and take 7 g of 2-4 mm bovine cancellous bone mineral particles and mix them.

[0232] Simulated body fluid (normal saline, NS) dissolution test: According to the solid-liquid ratio of material to simulated body fluid (normal saline) of 0.1 g / 1.5 ml, that is, 30 ml of NS solution / 2 g of sample, the supernatant was collected at time points such as 24, 72, 168, and 336 hours, and the calcium, phosphorus, and magnesium ions were detected by medical biochemical analyzer. The pH value was detected by test paper. At the 24 and 72 hour time points, 30 ml of NS solution was added; at the end of the experiment at 168 hours (1 week), the particles were removed; and dried at 95 for 24 hours.

[0233] PBS dissolution and sedimentation experiments: Using a solid-liquid ratio of 0.1 g / 1 ml (60 ml PBS solution per 2 g sample) of material to simulated body fluid (PBS), the supernatant was collected at 24, 72, 168, and 336 hours and analyzed for calcium, phosphorus, magnesium, and pH using a medical biochemical analyzer. 60 ml of PBS solution was added at 24 and 72 hours. At 168 hours (1 week), 120 ml of PBS solution was added. Dissolution and sedimentation continued for 336 hours (2 weeks). At the end of the experiment, the pellets were removed. The solution from the pellets after the dissolution and sedimentation experiments was pooled in a beaker. After sedimentation, the supernatant was carefully removed by aspiration. The pellets and pellets were dried in a 95°C incubator for 24 hours. The pellets and pellets were weighed and the dissolution and sedimentation rates were calculated. Powder diffraction elemental analysis was performed on the pellets and pellets.

[0234] Results: Dissolution was observed early in the simulated body fluid (normal saline) dissolution experiment, and a stable microenvironment with high calcium content (8-13.59 [2-2.67 mmol / L]) and magnesium content (>1.2 mmol / L) was continuously formed. The pH remained approximately 10-12 at all immersion times in all simulated body fluids (NS / PBS). In the PBS dissolution deposition experiment, samples 2304121, 2304122, and 2304123 exhibited typical calcium-phosphorus flocculent deposits early on, which gradually increased while the calcium and magnesium concentrations in the solution gradually decreased (the high calcium-magnesium-rich microenvironment in the solution provided the biochemical basis for the formation of magnesium-containing calcium-phosphorus deposits). Dissolution rates were 29.5%, 21.5%, and 12%, respectively, and were positively correlated with the ratio of cuttlefish bone to calcium sulfate in the samples. After two weeks of PBS dissolution deposition, the samples exhibited good calcium-phosphorus deposition (14.16%), primarily composed of hydroxyapatite and a small amount of calcium pyrophosphate.

[0235] Example 13:

[0236] 2304131: (Cuttlefish bone + calcium sulfate) / HA = 1 / 1; Cuttlefish bone / calcium sulfate = 1 / 11; Take 1 gram of cuttlefish bone mineral powder, 11 grams of calcium sulfate hemihydrate, and 0.47 grams of magnesium sulfate heptahydrate, add 12 mL of distilled water, stir and squeeze to form a putty, add 6 grams each of 0.35-1 mm and 2-4 mm bovine cancellous bone mineral particles, stir evenly, squeeze and mix into a concrete-like state, then batch and granulate, and let the material stand at 35°C; dry at 95°C for 24 hours to obtain 24.66 grams of 2304102 material, and perform powder diffraction composition analysis on the particles.

[0237] 2304132: Take 4.11, one-sixth of the total mass of 2304131, which contains 2 grams of HA, 1 / 6 gram of cuttlefish bone mineral powder, and 11 / 6 grams of calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 2, and take 2 grams of 2-4 mm bovine cancellous bone mineral and mix it with it.

[0238] 2304133: Take one-twelfth of the total mass of 2304131, which is 2.06 grams, containing 1 gram of HA, 1 / 12 gram of cuttlefish bone mineral powder, and 11 / 12 grams of calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 4, and take 3 grams of 2-4 mm bovine cancellous bone mineral and mix it with it.

[0239] 2304133: Take one-twenty-fourth of the total mass of 2304131, or 1.03 grams, containing 0.5 grams of HA, 1 / 24 grams of cuttlefish bone mineral powder, and 11 / 24 grams of calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 6, and take 2.5 grams of 2-4 mm bovine cancellous bone mineral and mix it with it.

[0240] Simulated body fluid (normal saline) dissolution test: The method was the same as Example 11. Results: After one week of immersion, none of the materials showed significant disintegration, and the pH value gradually decreased during the normal saline immersion experiment. The two-week dissolution rate was 16.5% for 2304133, 12% for 2304132, and 9% for 2304133. The dissolution rate was positively correlated with the ratio of cuttlefish bone and calcium sulfate in the material.

[0241] PSB dissolution and precipitation experiment: The method was the same as in Example 11. Results: The particles had perfect morphology. After one week of dissolution, no significant dissolution or disintegration was observed for any of the materials (possibly due to the effect of magnesium sulfate in cement). The pH value was approximately 6-10 after 24 hours of immersion. No obvious cloud-like deposits were observed during the early stages of PBS immersion, but the deposits gradually increased. In the middle and late stages, cloud-like deposits gradually appeared and increased. At two weeks, the thickness of the cloud-like deposits was 2304131, 2304132, and 2304133. The dissolution rates for 2304133, 2304132, and 2304133 were 32.5%, 28.5%, and 16%, respectively, for 2304133, respectively. The total deposition rate was 9.74%, and the primary apatite deposits were octacalcium phosphate, followed by Ca5(PO4)3(OH).

[0242] Example 14:

[0243] 2304191: (Cuttlefish bone + calcium sulfate) / HA = 1 / 1; Cuttlefish bone / calcium sulfate = 3 / 8; Take 3 grams of cuttlefish bone mineral powder and 8 grams of calcium sulfate hemihydrate, add 9.5 mL of distilled water, stir and squeeze to form putty, add 5.5 grams of bovine cancellous bone mineral particles with particle size of 0.35-1 mm and 2-4 mm, stir evenly, squeeze and mix into a concrete-like state, then batch and granulate, let the material stand at 35℃; dry at 95℃ for 24 hours to obtain 22.21 grams of 2304191 material, and perform powder diffraction composition analysis on the particles. 2304191

[0245] Ca5( P O4 )3( OH ) 45.9%

[0246] Ca ( S O4 ) ( H2O ) 0.5 3.9%

[0247] Ca (S O4) 45.1%

[0248] Ca ( OH )2 5.1%.

[0249] 2304192: Take two-elevenths of the weight of 2304191, which contains 2 grams of HA and 2 grams of cuttlefish bone mineral powder and calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 2, and take 2 grams of 2-4 mm bovine cancellous bone mineral and mix it with it.

[0250] 2304193 takes one eleventh of the weight of 2304191, which contains 1 gram of HA and 1 gram of cuttlefish bone mineral powder and calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 4, and take 3 grams of 2-4 mm bovine cancellous bone mineral and mix it with it.

[0251] 2304194 takes one twenty-second part of the weight of 2304131, which contains 0.5 g of HA and 0.5 g of cuttlefish bone mineral powder and calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 6, and take 2.5 g of 2-4 mm bovine cancellous bone mineral and mix it with it.

[0252] Dissolution reduction experiment in simulated body fluid (normal saline, NS): The method was the same as in Example 11. Dissolution reduction occurred early in the experiment, and a stable microenvironment with high calcium (>8 (2-2.67 mmol / L)) and magnesium (>0.9 mmol / L) concentrations was continuously formed. The dissolution reduction rates over two weeks were 44% (2304191), 32% (2304192), 13% (2304193), and 8% (2304194), respectively. The dissolution reduction rate was positively correlated with the ratio of cuttlefish bone to calcium sulfate in the material.

[0253] PNS dissolution and sedimentation experiment: According to the solid-liquid ratio of material to simulated body fluid (PNS) of 0.1 g / 1.5 ml, that is, 30 ml of PNS solution / 2 g of sample, the supernatant was taken at 24, 72, 168, 336, and 504 hours, and the calcium, phosphorus, and magnesium ions were detected by medical biochemical analyzer, and the pH value was detected with test paper. At 24 hours, 30 ml of PNS solution was added; at 72 and 168 hours, 60 ml of PNS solution was added; and at 336 hours, 120 ml of PNS solution was added; when the dissolution and sedimentation reached 504 hours, the particles were taken out, dried at 95 for 24 hours, weighed, and the dissolution rate was calculated. Results: Obvious cloud-like deposits were observed in the early stages of observation, such as at 24, 72, and 168 hours. The pH during the deposition experiment was 9-11. After removing the particles from the beaker, the solution after the dissolution and deposition experiment was concentrated in a beaker. After precipitation, the supernatant was carefully removed by aspiration. The sedimentation solution and particles were dried in a 95°C constant temperature oven for 24 hours, weighed, and the dried sediment was analyzed by powder diffraction. The deposition rate was calculated. In the PNS dissolution and deposition experiment, 2304191-2304194 exhibited typical magnesium-containing calcium phosphate flocculent deposits early in the experiment ( Figure 9 ), and the amount (thickness) of calcium phosphate floccules gradually increased with the duration of the dissolution and deposition experiments. The amount (thickness) of calcium phosphate floccules 2304194, 2304193, 2304192, and 2304191 increased in that order (i.e., the greater the cuttlebone and calcium sulfate content in the composite, the greater the amount of calcium phosphate floccules). Simultaneously, the calcium and magnesium concentrations in the PNS solution gradually decreased, suggesting that calcium and magnesium ions provide the biochemical basis for the continuous deposition of calcium and phosphate. The dissolution and deposition rates over three weeks were 48% (2304191), 36% (2304192), 23% (2304193), and 14% (2304194), respectively. These rates were positively correlated with the proportions of cuttlebone and calcium sulfate in the composite. The total calcium and phosphate deposition rate over three weeks was 12.21%, with the calcium and phosphate deposits consisting of hydroxyapatite.

[0254] Example 15:

[0255] 2304121: Calcium sulfate hemihydrate / bovine cancellous bone granules (1:2 ratio); cuttlebone powder / calcium sulfate hemihydrate (1:1 ratio). 6g cuttlebone powder, 6g sulfuric acid hemihydrate; 12g bovine cancellous bone granules (1-4mm diameter). Combine calcium sulfate and normal saline (9ml) and stir repeatedly, then add cuttlebone powder and mix and squeeze to a slurry consistency. Add bovine cancellous bone granules and stir and squeeze to separate the granules. Allow the material to stand at 35°C for 24 hours. Dry at 95°C for 24 hours to obtain 23.06g of material 2304121 (the main structure is bovine cancellous bone granules coated with cuttlebone powder and calcium sulfate hemihydrate).

[0256] 2304122: Take one-fourth of the amount of dry 2304121, i.e. 5.765 g, containing 3 g of HA, 1.5 g of cuttlefish bone mineral powder and 1.5 g of calcium sulfate (calcium sulfate / HA = 1 / 4); add 3 g of bovine cancellous bone mineral particles (1-3 mm in diameter) and mix well to obtain 2304122.

[0257] 2304123: Take 2.88 g, one-eighth of the dry weight of 2304121, containing 1.5 g of HA, 0.75 g of cuttlefish bone powder, and 0.75 g of calcium sulfate; set (calcium sulfate / HA = 1 / 4); add 4.5 g of bovine cancellous bone granules (1-3 mm in diameter) and mix thoroughly to obtain 2304123.

[0258] 2304141: (Cuttlefish bone + calcium sulfate) / HA=1 / 1 [Calcium sulfate / HA=8 / 11]; Cuttlefish bone / calcium sulfate=3 / 8; Take 6 grams of cuttlefish bone mineral powder, 16 grams of calcium sulfate hemihydrate, add 17.5 ml of distilled water, stir and squeeze to mix into putty, add 22 grams of bovine cancellous bone mineral particles with a diameter of 1-4 mm, stir evenly, squeeze and mix into a concrete-like state, and then granulate. Let the material stand at 35℃ for 24 hours; dry at 95℃ for 24 hours to obtain 37.56 grams of 2304141 material.

[0259] 2304142: Take 6.829, two-elevenths of the total mass of 2304141, which contains 4 grams of HA and 4 grams of cuttlefish bone mineral powder and calcium sulfate; set (cuttlefish bone + calcium sulfate) / HA = 1 / 2 [calcium sulfate / HA = 1 / 4], and take 4 grams of 1-4 mm bovine cancellous bone mineral to mix with it.

[0260] 2304143: Take 3.41, one eleventh of the total mass of 2304141, i.e. 2 grams of HA, 1 gram of cuttlefish bone mineral powder, and 1 gram of calcium sulfate each; set (cuttlefish bone + calcium sulfate) / HA = 1 / 3 [calcium sulfate / HA = 1 / 6], and mix with 4 grams of 1-4 mm bovine cancellous bone mineral.

[0261] 2304261: (Cuttlefish bone + calcium sulfate) / HA = 1 / 1; Cuttlefish bone / calcium sulfate = 1 / 10 [calcium sulfate / HA = 10 / 11]; take 1 gram of cuttlefish bone mineral powder, 10 grams of calcium sulfate hemihydrate; 1.0 grams of magnesium hydrogen phosphate, 1.5 grams of strontium sulfate; add 7.5 milliliters of distilled water, stir and squeeze to form putty, add 11 grams of 1-4 mm bovine cancellous bone mineral particles, stir evenly, squeeze and mix into a concrete-like state, then batch and granulate, let the material stand at 35°C for 24 hours; dry at 95°C for 24 hours to obtain 23.92 grams of 2304261 material.

[0262] 2304262: Take 2 / 10th of the mass of 2304261 (4.78g), which contains approximately 2.2g of HA and 2.2g of cuttlefish bone mineral powder and calcium sulfate. Set (cuttlefish bone + calcium sulfate) / HA = 1 / 2 [calcium sulfate / HA = 5 / 11] and mix with 2.2g of 1-4mm bovine cancellous bone mineral.

[0263] 2304263: Take 2 / 10th of the mass of 2304261 (2.39 g), containing approximately 1.1 g HA and 1.1 g cuttlebone mineral powder and calcium sulfate; set (cuttlebone + calcium sulfate) / HA = 1 / 4 [calcium sulfate / HA = 2.5 / 11], and mix it with 3.3 g of 1-4 mm bovine cancellous bone mineral.

[0264] Control group 1 2305021: bovine cancellous bone mineral particles / calcium sulfate hemihydrate mass ratio 1:1; prepared sulfuric acid hemihydrate 15 grams; bovine cancellous bone mineral particles (diameter 1-4 mm) 15 grams; take prepared sulfuric acid hemihydrate 15 grams and normal saline 9 ml, stir repeatedly, then add bovine cancellous bone mineral particles, stir, push and separate the particles, let the material stand at 35 ° C for 24 hours; dry at 95 ° C for 24 hours to obtain 2305021 material (the main structure is the surface of bovine cancellous bone particles coated with calcium sulfate hemihydrate) 29.47 grams.

[0265] Materials of control group 2: 1-4 mm bovine cancellous bone mineral.

[0266] Extraction of artificial bone material by dissolution experiment

[0267] Through the method of dissolution experiment: the material was immersed in α-MEM culture medium, the pH was adjusted to 7.40, and the mass volume ratio was mixed at 0.2g / mL. The shaker speed was 100r / min, and the extract was obtained at the time point of 14 days. The extract was then used for cell osteogenesis experiment.

[0268] Cell osteogenesis assay:

[0269] (1) ALP alkaline phosphatase assay: The extracts from different materials were used to culture 3T3 cells with osteogenic induction solution for 14 days, and then ALP staining was performed. ALP activity was determined using an ALP microplate assay kit (Beyotime, China), and the osteogenic activity of different artificial bone materials was directly observed under an optical microscope.

[0270] (2) Alizarin red staining: Calcium deposition (mineralization) was determined using Alizarin red S staining. Cultured 3T3 cells were fixed in 4% paraformaldehyde at 37°C for 15 minutes and then stained with 1% Alizarin red solution (Sigma) for 45 minutes. The samples were then washed with PBS to remove nonspecific staining and observed directly under a light microscope. The osteogenic activity of the artificial bone material was determined by the intensity of Alizarin red staining.

[0271] Results: All experimental groups showed better osteogenic activity than the control group 1, among which the 2304141-2304143 and 2304261-2304263 series had the best osteogenic activity, followed by the 2304121-2304123 series and the 2305021 series. Figure 10 ).

[0272] Example 16: Editing Completed

[0273] 401231: The mass ratio of hemihydrated calcium sulfate / bovine cancellous bone mineral particles is 1:1; the mass ratio of cuttlebone bone mineral powder / hemihydrate calcium sulfate is 1.5:1, and the mass ratio of oxalic acid / cuttlebone bone mineral is 1 / 8. Ingredients: 8 grams of bovine cancellous bone mineral particles (particle size 1-3 mm), 8 grams of hemihydrated calcium sulfate, 12 grams of cuttlebone bone mineral powder; take 12 grams of cuttlebone bone mineral powder, 8 grams of hemihydrated calcium sulfate, and 1 gram of oxalic acid, mix well, add 28 milliliters of compound sodium chloride injection, and stir repeatedly to form a slurry, add 8 grams of bovine cancellous bone mineral particles to mix, stir repeatedly to blend, and then granulate, dry at 95℃ for 24 hours to obtain composite particles 401231 with the inner core being bovine cancellous bone mineral particles and the surface being coated with cuttlebone bone mineral powder + calcium sulfate.

[0274] Take one-eighth of the mass of 401231, containing 2.0 g of HA, 2.0 g of calcium sulfate, and 3 g of cuttlefish bone powder; set the calcium sulfate / HA ratio to 1 / 8; take 14 g of 1-3 mm bovine cancellous bone mineral and mix with it to obtain 401232;

[0275] Take 2.5 grams of materials 401231 and 401232 and immerse them in sodium chloride injection with a solid-liquid ratio of 2.5 grams / 25 ml of normal saline. Immerse for 7 days and detect the pH value to be about 8; the extract was biochemically analyzed and 16 metal elements were detected by ICP-MS method.

[0276] Biochemical analysis results:

[0277] 401231 total calcium 13.61 (2.00-2.67mmol / L), magnesium 2.19 (0.60-1.2mmol / L), phosphorus 0.02 (0.81-1.62mmol / L);

[0278] 401232 total calcium 13.52 (2.00-2.67mmol / L), magnesium 2.1 (2.00-2.67mmol / L), phosphorus 0.02 (2.00-2.67mmol / L);

[0279] ICP-MS test results of 16 metal ions in the extract: 401231:

[0281] Calcium 32.43 (1.15-2.10) mmol / L

[0282] Magnesium 2.57 (1.13-2.09) mmol / L

[0283] Iron <0.10 (4.91-9.47) mmol / L

[0284] Copper <0.10 (6.30-28.35) μmol / L

[0285] Zinc 9.62 (65.65-126.72) μmol / L

[0286] Lead <0.10 (<200) ug / L

[0287] Chromium 38.55 (<10) ug / L

[0288] Selenium 25.56 (100-340) ug / L

[0289] Molybdenum 7.44 (<3.30) ug / L

[0290] Manganese 4.13 (3.0-36) ug / L

[0291] Arsenic 1.98 (<23) ug / L

[0292] Lithium 50.39 (<72) ug / L

[0293] Strontium 58837.52 (10-45.00) ug / L

[0294] Cobalt <0.10 (<3.0) ug / L

[0295] Cadmium <0.10 (<5.0) ug / L 401232:

[0297] 1 Calcium 40.98 (1.15-2.10) mmol / L

[0298] 2 magnesium 3.77 (1.13-2.09) mmol / L

[0299] 3 Iron <0.10 (4.91-9.47) mmol / L

[0300] 4 Copper <0.10 (6.30-28.35) μmol / L

[0301] 5 Zinc 66.27 (65.65-126.72) umol / L

[0302] 6 Lead 10.21 (<200) ug / L

[0303] 7 chromium 31.64 (<10) ug / L

[0304] 8 Selenium 28.17 (100-340) ug / L

[0305] 9Molybdenum 2.94 (<3.30) ug / L

[0306] 10 Manganese 1.08 (3.0-36) ug / L

[0307] 11 Arsenic 0.54 (<23) ug / L

[0308] 12 Lithium 28.86 (<72) ug / L

[0309] 13strontium 36920.50 (10-45.00)ug / L

[0310] 14 Cobalt <0.10 (<3.0) ug / L

[0311] 15 Cadmium <0.10 (<5.0) ug / L

[0312] 16 Mercury <0.10 (<14.90) ug / L

[0313] In the NS immersion experiment, dissolution is visible to the naked eye. The biochemical and ICP-MS tests of 16 metal ions and pH value tests of the 401231 and 401232 immersion solutions can form a slightly alkaline environment with high calcium, high strontium, rich magnesium and rich chromium.

[0314] Example 17:

[0315] 312121: Set the ratio of (cuttlefish bone powder + calcium sulfate) / HA to 1 / 3; cuttlefish bone powder / calcium sulfate to 1 / 4; and cuttlefish bone powder / (cuttlefish bone powder + calcium sulfate + bovine cancellous bone particles) to 1 / 20. Mix 1 gram of cuttlefish bone powder, 4 grams of calcium sulfate hemihydrate, and 0.125 grams of oxalic acid with 7.5 milliliters of distilled water to form a slurry. Add 15 grams of 1-3 mm bovine cancellous bone particles and stir the mixture into a uniform slurry. Incubate at 35°C for 48 hours to obtain 312121 (21.02 grams of bovine cancellous bone particles coated with zinc-doped cuttlefish bone powder and calcium sulfate).

[0316] 312122: Set the ratio of (cuttlefish bone powder + calcium sulfate) / HA to 1 / 6; cuttlefish bone powder / calcium sulfate to 1 / 4; cuttlefish bone powder / (cuttlefish bone powder + calcium sulfate + bovine cancellous bone granules) to 1 / 35. Take one-quarter of the mass of 312121, or 5.25 grams (containing 0.25 grams of cuttlefish bone powder, 1 gram of calcium sulfate hemihydrate, and 3.75 grams of bovine cancellous bone granules), add 3.75 grams of bovine cancellous bone granules, and mix to obtain 31212 grams.

[0317] Take 2.5 grams of materials 312121 and 312122 and immerse them in sodium chloride injection with a solid-liquid ratio of 2.5 grams / 25 ml of normal saline. Soak for 2 days and test the pH value to about 9-10. The extract is subjected to biochemical analysis and 16 metal elements detection by ICP-MS method.

[0318] Biochemical analysis results:

[0319] Saline immersion test

[0320] 312121: pH 9-10 after 2 days, pH 9-10 after 4 days, pH 9-10 after 7 days

[0321] 312122: pH 9-10 after 2 days, pH 9-10 after 4 days, pH 9-10 after 7 days

[0322] Biochemical analysis of the extract from two-day saline immersion test:

[0323] 312121: calcium 14.20 mmol / L, magnesium 1.89 mmol / L, phosphorus 0.02 mmol / L

[0324] 312122: Calcium 14.15 mmol / L, Magnesium 1.69 mmol / L, Phosphorus 0.01 mmol / L

[0325] 16 cation tests of 7-day extract: 312121:

[0327] 1 Calcium 33.70 (1.15-2.10) mmol / L

[0328] 2 magnesium 1.97 (1.13-2.09) mmol / L

[0329] 3 Iron <0.10 (4.91-9.47) mmol / L

[0330] 4 Copper <0.10 (6.30-28.35) μmol / L

[0331] 5. Zinc 0.97 (65.65-126.72) μmol / L

[0332] 6 Lead 3.53 (<200) ug / L

[0333] 7 chromium 20.05 (<10) ug / L

[0334] 8 Selenium 8.95 (100-340) ug / L

[0335] 9Molybdenum 10.60 (<3.30) ug / L

[0336] 10 Manganese 0.60 (3.0-36) ug / L

[0337] 11 Arsenic <0.10 (<23) ug / L

[0338] 12 Lithium 50.55 (<72) ug / L

[0339] 13Sr 7563 (10-45.00) ug / L

[0340] 14 Cobalt <0.10 (<3.0) ug / L

[0341] 15 Cadmium <0.10 (<5.0) ug / L

[0342] 16 Mercury <0.10 (<14.90) ug / L 312122:

[0344] 1 Calcium 27.52 (1.15-2.10) mmol / L

[0345] 2 magnesium 1.77 (1.13-2.09) mmol / L

[0346] 3 Iron <0.10 (4.91-9.47) mmol / L

[0347] 4 Copper <0.10 (6.30-28.35) μmol / L

[0348] 5 Zinc 1.57 (65.65-126.72) umol / L

[0349] 6 Lead 2.68 (<200) ug / L

[0350] 7 chromium 13.30 (<10) ug / L

[0351] 8 Selenium 10.22 (100-340) ug / L

[0352] 9Molybdenum 8.87 (<3.30) ug / L

[0353] 10 Manganese 0.51 (3.0-36) ug / L

[0354] 11 Arsenic <0.10 (<23) ug / L

[0355] 12 Lithium 20.20 (<72) ug / L

[0356] 13strontium 3460.63 (10-45.00)ug / L

[0357] 14 Cobalt <0.10 (<3.0) ug / L

[0358] 15 Cadmium <0.10 (<5.0) ug / L

[0359] 16 Mercury <0.10 (<14.90) ug / L

[0360] Dissolution was visible to the naked eye in the NS immersion experiment. Biochemical tests, 16 metal ion tests by ICP-MS and pH value tests of the 312121 and 312122 immersion solutions showed that an alkaline microenvironment with high calcium, high strontium, rich magnesium and rich chromium was formed.

[0361] Example 18:

[0362] 23042611: Set (cuttlefish bone + calcium sulfate) / HA = 1 / 4; cuttlefish bone / calcium sulfate = 1 / 10; cuttlefish bone / (cuttlefish bone + calcium sulfate + HA) = 1 / 51; take 0.25 g of cuttlefish bone mineral powder and 2.5 g of calcium sulfate hemihydrate; add 4 ml of distilled water and stir to form a homogenous slurry, add 10 g of 1-3 mm bovine cancellous bone mineral particles, stir repeatedly and batch granulate. After initial solidification, let the material stand at 35°C for 24 hours [sun exposure for 2 hours, the temperature on the day is 13°C]. 23042611 material 13.09 g, the coating is thin as can be seen in the enlarged photo, and micropores are visible in some particles. Photo attached.

[0363] 23042612: Take 3.28g, one-fifth of the mass of 2304261, containing 2g HA, 0.5g calcium sulfate hemihydrate, and 0.05g cuttlebone mineral powder; set the calcium sulfate / HA ratio to 1 / 8 and the cuttlebone / (cuttlebone + calcium sulfate + HA) ratio to 1 / 9. Mix 2g of 1-4mm bovine cancellous bone mineral powder with the mixture to produce 23042612.

[0364] Material extraction: 5g material / 50ml distilled water for 4 days to test the pH value, then take the extract and send it to ICP-MS method for 16 metal elements detection;

[0365] pH test results:

[0366] 23042611: pH value of the extract after 4 days: 12;

[0367] 23042612: pH value of the 4-day extract was 12;

[0368] The results of metal element detection of the 4-day extract by ICP-MS: 23042611:

[0370] 1 Calcium 16.27 (1.15-2.10) mmol / L

[0371] 2.25 (0.60-1.20) mmol / L magnesium

[0372] 3 Iron <0.10 (4.91-9.47) mmol / L

[0373] 4 Copper 0.12 (6.30-28.35) umol / L

[0374] 5. Zinc <0.10 (65.65-126.72) μmol / L

[0375] 6 Lead 6.22 (<200) ug / L

[0376] 7 chromium 1.65 (<10) ug / L

[0377] 8 Selenium 3.35 (100-340) ug / L

[0378] 9Molybdenum 1.50 (<3.30) ug / L

[0379] 10 Manganese <0.17 (3.0-36) ug / L

[0380] 11 Arsenic 0.25 (<23) ug / L

[0381] 12 Lithium 1.76 (<72) ug / L

[0382] 13Sr 2240 (10-45.00) ug / L

[0383] 14 Cobalt <0.10 (<3.0) ug / L

[0384] 15 Cadmium 0.15 (<5.0) ug / L

[0385] 16 Mercury 0.15 (<14.90) ug / L 23042612:

[0387] 1 Calcium 14.01 (1.15-2.10) mmol / L

[0388] 2 magnesium 2.03 (0.60-1.20) mmol / L

[0389] 3 Iron <0.10 (4.91-9.47) mmol / L

[0390] 4 Copper <0.10 (6.30-28.35) μmol / L

[0391] 5. Zinc <0.10 (65.65-126.72) μmol / L

[0392] 6 Lead 2.97 (<200) ug / L

[0393] 7 chromium <0.60 (<10) ug / L

[0394] 8 Selenium 1.93 (100-340) ug / L

[0395] 9Molybdenum 1.52 (<3.30) ug / L

[0396] 10 Manganese <0.17 (3.0-36) ug / L

[0397] 11 Arsenic 0.24 (<23) ug / L

[0398] 12-lithium 0.12 (<72) ug / L

[0399] 13 Strontium 2104.00 (10-45.00)ug / L

[0400] 14 Cobalt <0.10 (<3.0) ug / L

[0401] 15 Cadmium <0.10 (<5.0) ug / L

[0402] 16 Mercury <0.10 (<14.90) ug / L

[0403] Results: Dissolution was visible in the NS immersion experiment. Biochemical, 16 metal ion tests by ICP-MS and pH value tests of the immersion fluids of 23042611 and 23042012 showed that a high calcium, high strontium, magnesium and alkaline microenvironment was formed.

[0404] The embodiment described above is only a preferred solution of the present invention and does not limit the present invention in any form. Other variations and modifications are possible without exceeding the technical solution described in the claims.

Claims

1. An orthopedic tissue filling material, characterized in that: The preparation raw materials include cuttlefish bone mineral powder, bovine or porcine cancellous bone mineral particles and calcium sulfate, the mass ratio of cuttlefish bone mineral powder to calcium sulfate is 1:1-10, and the mass ratio of the total mass of cuttlefish bone mineral powder + calcium sulfate to the bovine or porcine cancellous bone mineral particles is 1:1-5; Cuttlefish bone mineral powder, calcium sulfate and blending liquid are stirred and mixed to form a coating slurry, and then stirred and coagulated with bovine or porcine cancellous bone mineral particles, and granulated to form an orthopedic tissue filling material; Or the cuttlefish bone mineral powder, calcium sulfate and the blending liquid are stirred and mixed to form a coating slurry, and then stirred and coagulated with part of the bovine or porcine cancellous bone mineral particles, and the particles are divided to form particles with the cuttlefish bone mineral powder and the calcium sulfate coating on the surface, and the particles with the cuttlefish bone mineral powder and the calcium sulfate coating on the surface are then mixed with the remaining bovine or porcine cancellous bone mineral particles to form an orthopedic tissue filling material; Cuttlefish bone mineral powder + calcium sulfate total mass: blending liquid = 1g: 0.7-1.5mL, the blending liquid is physiological saline or distilled water; The tissue filling material uses bovine or porcine cancellous bone mineral particles as a three-dimensional skeleton material and a mixture of cuttlefish bone mineral powder and calcium sulfate as a degradable coating material; The preparation method of the bovine or porcine cancellous bone mineral particles is as follows: (1) Cutting the cancellous bone of bovine or porcine femoral condyle into bone blocks with a thickness of 1 to 4 cm to obtain raw bone; (2) Place the raw bone in distilled water and cook it in a pressure cooker for 35-45 minutes, then wash it with 50-70℃ water; repeat this step 5-6 times; (3) drying the raw bone treated in step (2) at 80-120° C. for 12-24 hours, and then placing it in a calcining furnace and calcining it at 900-1200° C. for 6-12 hours. After cooling, the raw bone is obtained as bovine calcined cancellous bone mineral, which is then crushed and sieved to obtain bovine or porcine cancellous bone mineral particles; The preparation method of the cuttlefish bone mineral powder is: (1) Wash the cuttlefish bone with water at 50-70℃, then dry it at 80-120℃ for 12-24 hours, then remove the outer shell and take out the inner core of the cuttlefish bone; (2) The cuttlefish bone core is placed in a crucible, and then placed in a calcining furnace, and calcined at 800-1200° C. for 3-6 hours. After cooling, the cuttlefish bone mineral powder with uniform particles is obtained by stirring.

2. The orthopedic tissue filling material according to claim 1, characterized in that: The calcium sulfate is calcium sulfate hemihydrate.

3. The orthopedic tissue filling material according to claim 1, characterized in that: The particle size of the bovine or porcine cancellous bone mineral particles is 0.2-6 mm.

Citation Information

Patent Citations

  • Method and arrangement for receiving data

    CA2292534A1

  • Apparatus and methods for droplet microchemistry

    CA2302271A1

  • Cuttlefish bone source biphase calcium phosphate bioactive bone repair material as well as preparation method and application thereof

    CN115321501A